Integrated genetic and clinical investigation of autosomal dominant hereditary uterine leiomyomas: genotype-phenotype correlation in a pakistani family - Aman Ullah; Nabgha-e -Amen; Sadaf Iftikhar (Molecular Biology Reports, 2026)

Insights on inflammatory pathways and their cross-talk: a comprehensive review on asthma - Sadaf Naz; Aimen Wajid; Marya Nawaz Malik; Muhammad Khalid Tipu (Molecular Biology Reports, 2026)

A CLN8 biallelic missense variant causes epilepsy with severe treatment-resistant psychosis - Rimsha Zulfiqar; Ambreen Kanwal; Maham Hameed; Amina Iftikhar; Go Hun Seo; Sadaf Naz (Molecular Genetics and Genomics, 2026)

Nature-Inspired Nanocomposites for Toxic Heavy Metals Removal: An Overview - Mudassar SanaUllah; Awais Ali Aslam; Abhishek Thakur; Sania Amjad; Shahzaib Ishfaq; Sadaf Ul Hassan; Usman Haidar; Muhammad Shahid Nazir; Mahmood Ahmed; Marek Kowalczuk (Reviews of Environmental Contamination and Toxicology, 2026)

Protective effects of Coagulansin-A against LPS-induced inflammatory and oxidative stress responses in human lung epithelial cells - Sadaf Naz; Umakant Yadav; Sidra Faiz; Muhammad Usama Mazhar; Syeda Rida Zainab; Rizwan Ul Haq; Fadi Khasawneh; Ihsan Ul Haq; Muhammad Khalid Tipu; Lin Zhu (Toxicon, 2026)

Mitigation of aflatoxin B1-induced toxicopathology and immunosuppression in broilers using a multimodal antioxidant formulation - Muhammad Asad Ali; Muhammad Abdullah Arshad; Aisha Khatoon; Muhammad Kashif Saleemi; Shafia Tehseen Gul; Muhammad Umar Ijaz; Sadaf Faiz; Aneela Amin (Mycotoxin Research, 2026)

Exploring the synergistic effect of Pseudomonas monteilii on the growth promotion of mangrove isolated cyanobacterium Leptolyngbya lignicola - Karisma Dash; Sadaf Tanweer; Bhabatarini Panda (Archives of Microbiology, 2026)

Oxidative and reductive mechanisms for the photocatalytic degradation of per- and polyfluoroalkyl substances (PFAS): A critical review - Jyoti; Sadaf Yasmeen; Mario Bragaglia; Francesca Nanni (Journal of Environmental Chemical Engineering, 2026)

Biomass-derived MOF@cellulose composites for sustainable separation and energy applications - Sadaf Zulfiqar; Changjiang Liu; Zunaira Zulfiqar; Aamir Razaq; Khair Muhammad; Tianzhen Zhu; Yang Wang (Journal of Environmental Chemical Engineering, 2026)

Engineering MXene-based platforms for electrocatalytic CO2 and N2 reduction reactions; synthesis, modification strategies, and mechanistic insights - Sami Ur Rahman; Saeed Anwar; Awal Noor; Sadaf Qayyum; Yelubay Madeniyet; Niaz Muhammad (Journal of Environmental Chemical Engineering, 2026)

Advances in carbohydrate polymer-stabilized silver nanoparticles for catalysis - Sonia Sadaf; Faiza Bibi; Ahmad Irfan; Robina Begum; Zahoor H. Farooqi (Carbohydrate Polymers, 2026)

Sodium butyrate supplementation improves growth performance, gut health, hepatic enzyme activities, and disease resistance against Aeromonas hydrophila in Labeo rohita - Aafaq Younas; Mahroze Fatima; Syed Zakir Hussain Shah; Noor Khan; Wazir Ali; Ayesha Khizar; Ayesha Tanveer; Sadaf Khadim (Veterinary Research Communications, 2026)

Exploring the Potential of Synechocystis sp. PCC 6803 for P(3HB-co-3HV-co-4HB) Terpolymer Production - Sadaf Tanweer; Bhabatarini Panda (Current Microbiology, 2026)

Bacillus subtilis MGRP21 mitigates chromium induced oxidative stress and enhances biomass of Brassica napus L - Shurmeen Qammar; Syeda Sadaf Zehra; Muhammad Naveed Aslam; Anam Moosa; Phyu Shin Thant; Tahir Mahmood; Hongwei Zhao (Physiological and Molecular Plant Pathology, 2026)

Household Solid Fuel Combustion-Related PAH Exposure in Rural Northern China: Associations of Phenanthrene Metabolites with DNA Damage and Systemic Inflammation - Sulin Chen; Yunxuan Gu; Hongmei Xu; Sadaf Gulzar; Miaoqian Li; Yifei Xu; Min Gao; Jian Sun; Zhenxing Shen (Atmospheric Environment, 2026)

Elevated Carbon Dioxide Modifies Root Metabolic Activities and Sustains Wheat Grain Yield Under Drought Stress - Aneela Ulfat; Saima Ashraf; Habib Ali; Aasma Noureen; Sadaf Kayani; Imran Haider Shamsi (Journal of Soil Science and Plant Nutrition, 2026)

Wound healing and antibacterial properties of albumin-based hydrogel supplemented with Ajuga bracteosa extracts - Sadaf Azad Raja; Saiqa Andleeb; Zeerish Faisal; Marwa Naeem; Sana Javed; Nadia Gillani; Sumathi Jones; Daratu Eviana Kusuma Putri; Soundar Rajan Kulandhaivel; Soon Woong Chang; Balasubramani Ravindran; Jesudass Joseph Sahayarayan (Journal of Pharmaceutical Innovation, 2026)

Biocultural structuring of ethnomedicinal knowledge across cultural and altitudinal gradients in the Western Himalayas - Choudhary Muhammad Babar; Sadaf Kayani; Musheerul Hassan; Ivana Vitasović-Kosić; Sayed Afzal Shah (Plant Biosystems, 2026)

Exploring ethyl methane sulphonate induced, L-cysteine HCl resistant Bacillus subtilis putative mutant and its immobilization for enhanced acetoin synthesis - Muhammad Usman Ahmad; Sikander Ali; Noor Ul Ain; Nabeera Shahzadi; Maryam Mustaid; Mahwish Arshad; Sadaf Ahmad; Bakar Bin Khatab Abbasi; Ali Irfan; Yousef A. Bin Jardan (Archives of Microbiology, 2026)

First molecular record of Panaeolus subbalteatus (Psathyrellaceae, Agaricales) from Pakistan - Saliha Rukhsar; Nousheen Yousaf; Sadaf; Mahneem Fazal; Muhammad Hanif; Murad Muhammad; Dilfuza Egamberdieva; Wen-Jun Li (Antonie van Leeuwenhoek, 2026)

Gastrointestinal Parasitism in Cattle and Water Buffaloes in Pakistan: Prevalence and Associated Risk Factors - Tawseef Khan; Nasreen Nasreen; Sadaf Niaz; Adil Khan; Ayman A. Swelum; Ruhoo Ullah; Wajid Ali; Mourad Ben Said (Acta Parasitologica, 2026)

Green synthesis and antifungal evaluation of Moringa oleifera-mediated iron oxide nanoparticles against Rhizopus stolonifer infecting Coleus scutellarioides - Sadaf Anwaar; Maryam Bibi; Ansa Muqaddas; Ayesha Arif; Osama Alam; Tauseef Anwar; Huma Qureshi; Hossam S. El-Beltagi; Muydinjon M. Muminov; Mohammed S. Alotaibi; Khudiyev Orkhan; Ibtisam M. Alsudays; et al. (Folia Microbiologica, 2026)

Food security dynamics in South Asia: a multi-method analysis using Random Forest and Error Trend Seasonal models - Muhammad Atiq-ur-Rehman; Sadia Mustafa; Ayesha Hussain; Irfan Hussain Khan; Fatima Akhtar; Sadaf Javed; Azma Batool (Environment, Development and Sustainability, 2026)

Biochemical and computational characterization of a recombinant catalase from Kocuria rhizophila for degradation of hydrogen peroxide in textile wastewater - Asma Zafar; Hira Mubeen; Sadaf Hameed; Mahjabeen Khan; Hafsa Sohail; Maheen Zaka; Muhammad Nauman Aftab; Anuga Liyanage (Antonie van Leeuwenhoek, 2026)

Exploration of phenotypic and genetic diversity of different guava genotypes based on Inter Simple Sequence Repeat (ISSR) markers - Haleema Sheeren; Beenish Aftab; Farah Nazim; Aamna Ishaq; Mahroze Fatima; Sadaf Aman (South African Journal of Botany, 2026)

Acceptance of water reuse adoption in small communities: analysis of driving factors and policy preferences - Yu Wang; Sadaf Mehrabi; Kaoru Ikuma (Environmental Research, 2026)

A data-driven workflow for automated life cycle assessment in building refurbishment - Sadaf Gachkar; Darya Gachkar; Antonio García Martínez; Cecilio Angulo Bahón (Energy and Buildings, 2026)

Development of New Fuzzy Multi-objective Optimization Algorithm (F-MOICA3D) for Quantitative-Qualitative Sustainable Operation of Water Resources Based on 3D Response Space - Sadaf Mavali; Arash Azari (Water Resources Management, 2026)

Identification of Prognostic-Related Genes in Acute Myeloid Leukemia: A Study Based on TCGA Data Analysis - Fatemeh Sadat Shafiei; Saeid Abroun; Sadaf Vahdat; Ali Arash Anoushirvani; Mohammad Rafiee (Biochemical Genetics, 2026)

Mapping bioactive response pathways to cold plasma processing in food matrices: mechanisms, hybrid processing, and applications - Sadaf Mustafa; Xiao Yang; Kevin M. Keener; Jun-Hu Cheng (Food Research International, 2026)

Assessment of Coagulansin-A’s therapeutic potential and safety in an ovalbumin (OVA) induced airway inflammation model - Sadaf Naz; Muhammad Usama Mazhar; Aimen Wajid; Rimsha Noor; Lin Zhu; Muhammad Khalid Tipu (Inflammopharmacology, 2026)

Innovative methodologies for elucidating bushfire smoke-induced pathophysiological mechanism - Keshav R. Paudel; Karl J. Hegarty; Jesus Shrestha; Kurtis F. Budden; Nikhil T. Awatade; Tayyaba Sadaf; Vamshikrishna Malyla; Shafagh Waters; Paris C. Papagianis; Jane E. Bourke; Peter A. Wark; Philip M. Hansbro (Science of The Total Environment, 2026)

Biomimetic surface architectures inspired by cacti: Progress in fog water harvesting systems - Muhammad Numan Nawaz; Sadaf Bashir Khan; Weifang Yuan (Journal of Environmental Chemical Engineering, 2026)

Dietary Hydrilla verticillata extract enhances growth and immune defense against Aeromonas hydrophila in Labeo rohita - Faiza Khanam; Mahroze Fatima; Syed Zakir Hussain Shah; Noor Khan; Wazir Ali; Sadaf Khadim; Sobia Nisa; Mehwish Khan (Veterinary Research Communications, 2026)

Fusarium decemcellulare and F. annulatum, two emerging canker pathogens of fig trees and their potential pathogenicity on some fruit trees - Sadaf Sardooei; Zeinab Bolboli; Moslem Jafari; Reza Mostowfizadeh-Ghalamfarsa (Journal of Plant Diseases and Protection, 2026)

Integration of the Human Development Index into carbon accounting to enhance the equity and efficiency of emission allocations - Sadaf Amin; Xinkun Wang; Yiyi Cao; Yi-Ming Wei; Mimi Gong; Zhen Zhou; Guohua Zou (ENGINEERING Environment, 2026)

Mechanistic and Synergistic Evaluation of Amodiaquine–Isometamidium Combination Against Trypanosoma evansi: Integrated In Silico–In-Vitro Insights - Waqas Ahmad; Naeem Rasool; Mehmood Ahmad; Muhammad Yasin Tipu; Tehreem Fayyaz; Usama Bin Naeem; Sadaf Aroosa; Rana Muhammad Zahid Mushtaq (Acta Parasitologica, 2026)

Carboxymethyl cellulose/sodium alginate composite films encapsulated with turmeric essential oil-in-water nanoemulsion and gallic acid for grapes preservation - Muhammad Abdur Rehman Shah; Rahmat Ali Khan; Hidayat Ullah Khan; Obaid Ur Rehman; Sadaf-Ilyas Kayani; Liaqat Zeb; Khalid Ali Khan; Asad Mukhtar; Shuhao Huo (Food Chemistry, 2026)

Carboxylated Graphene Oxide (CGO) Adsorbent as an Effective and Green Approach for Targeting As (III) with Improved Adsorption Characteristics - Khizar Hussain Shah; Gul Afshan Khan; Zaher Hashisho; Sadaf Sarfraz; Muhammad Fahad; Muhammad Kazim (Water, Air, & Soil Pollution, 2026)

CO2-activated supplementary cementitious materials: Microstructural densification, mechanical enhancement, and life cycle assessment of carbonated mortars - Sadaf Noshin; Wasim Abbass; Sajjad Mubin; Fahid Aslam; Rayed Alyousef (Journal of Cleaner Production, 2026)

Gum Acacia-grafted multifunctional fluorescent hydrogel for ultra-trace sensing and sustainable recovery of samarium(III) - Somya Sadaf; Mrinmoy Karmakar; Yati Sharma; Anirban Mandal; Chinmay Ghoroi (Chemical Engineering Journal, 2026)

Intraspecific and interspecific variation of Salvadora species (S. oleoides Decne. and S. persica L.) along an aridity gradient in dryland ecosystems - Ummar Iqbal; Atta Hussain Sahir; Muhammad Sharif; Abdul Wahab; Mehboob Ahmad; Muhammad Yousuf; Sadaf Rafiq; Sana Abid (Trees, 2026)

Microstructural adaptations of snow bush (Aerva javanica (Burm.f.) Juss. Ex Schult.) in desert ecosystems - Sana Abid; Ummar Iqbal; Muhammad Sharif; Sadaf Rafiq; Aisha Sana; Abdul Wahab; Mehboob Ahmad; Muhammad Yousuf (The Science of Nature, 2026)

Metformin-mediated modulation of epigenetic regulators in type 2 diabetes: A study on differential expression of DNMT1, TET1, OGG1, and AID genes - Sadaf Moeez; Syeda Kiran Riaz; Tanveer Ahmed Qaiser; Juneda Sarfraz; Asif Naseer; Shafiul Haque (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Weather–Population Interactions of the Alien Pest Fall Armyworm (Spodoptera frugiperda): Field Evidence from Two Seasons - Sadaf Bashir; Pritha Ghosh (Journal of Crop Health, 2026)

Rab24 protein levels show dynamic changes in mouse tissues and human cancers - H. G. Mauricio Ramm; Farhad Ahmed; Sadaf Fazeli; Matthieu Bourgery; Martin Alexander Lopez; Lav Tripathi; Ilmo Leivo; Pernilla Syrjä; Eeva-Liisa Eskelinen (Cell and Tissue Research, 2026)
Rab24 is an unusual member of the Rab family of small GTPases, implicated in autophagy, endocytosis and cell division. In order to elucidate possible organ and age-specific roles of Rab24, we investigated tissue-specific levels of Rab24 in mice by western blotting and immunohistochemistry from postnatal day one to 9 months of age. In adult mice, the highest protein levels were found in the brain followed by the kidney, whereas lower levels were detected in the pancreas, spleen, liver, lung, heart, and skeletal muscle. Dynamic changes in Rab24 levels were observed during early postnatal development, with a sharp increase in the brain at postnatal day 14, after which the level remained high into adulthood. In the heart, skeletal muscle, pancreas and liver, higher Rab24 levels were observed during the first two postnatal weeks, after which the levels dropped and stayed low until adulthood. The age-dependent changes suggest age- and organ-specific regulation of Rab24 protein levels and possible organ-specific roles for Rab24 in development and maturation. Immunohistochemistry of the brain revealed that Rab24 was mostly present in neuronal cells in 1-month-old and older mice. Also, epithelial cells in several tissues showed high Rab24 levels. These results suggest possible roles for Rab24 in neuronal and epithelial maintenance. We further analysed immunohistochemical staining for RAB24 in human cancers and normal tissues. RAB24 staining in cancers of the breast and skin was higher than in the corresponding normal tissues, while it was reduced in cancers of the digestive system and the urinary tract. We also observed elevated RAB24 staining in medulloblastoma and neuroblastoma, two paediatric cancers of neuronal origin. In pancreatic neuroendocrine tumours that originate from islet cells, RAB24 levels were lower than in normal pancreatic islet cells. Collectively, our findings provide a comprehensive overview of RAB24 protein levels across mouse tissues and a wide spectrum of human cancers. The observed differences in RAB24 levels between cancer types and between malignant and normal tissues, suggest that RAB24 may serve as a potential diagnostic or differentiation marker in specific tumour types.

Correction: Designing gender-inclusive data systems in small-scale fisheries - Sarah J. Harper; Meryl Williams; Danika Kleiber; Mark Axelrod; Sangeeta Mangubhai; Elin Torell; Gonzalo Macho; Kafayat Fakoya; Nikita Gopal; Elena Ojea; Sarah Lawless; Nicole Franz; et al. (Ambio, 2026)

Designing gender-inclusive data systems in small-scale fisheries - Sarah J. Harper; Meryl Williams; Danika Kleiber; Mark Axelrod; Sangeeta Mangubhai; Elin Torell; Gonzalo Macho; Kafayat Fakoya; Nikita Gopal; Elena Ojea; Sarah Lawless; Nicole Franz; et al. (Ambio, 2026)

Perceived drought exposure in small communities of the United States: Demographic, attitudinal, and metric-based drivers - Sadaf Mehrabi; Ingrid Cintura Rojas; Antonio Arenas Amado; Yu Wang; Kaoru Ikuma (Science of The Total Environment, 2026)

Integration of mid and near-infrared spectroscopy for determining TPC and TFC in wheat varieties via multivariate analysis - Muhammad Zareef; Muhammad Arslan; Waqas Ahmad; Md Mehedi Hassan; Muhammad Naveed; Malik Muhammad Hashim; Sadaf Javaria; Quansheng Chen (Food Control, 2026)

pH-responsive MIL-101(Fe)/NiFe-LDH composite membranes for high-flux removal of cationic and anionic dyes in wastewater treatment - Shehriyar; Arslan Khurram; Abdul Jabbar; Muhammad Asim Khan; Wenhao Liu; Sadaf Mutahir; Akhtar Munir; Sameerah I. Al-Saeedi (Desalination, 2026)

Assessment of Chromium Toxicity and Health Risk in Vegetables Grown in Municipal Solid Waste-Amended Soils - Asma Ashfaq; Zafar Iqbal Khan; Toqeer Abbas; Saima Sadaf; Muhammad Arif; Muhammad Fayyaz; Iqra Parvez (Water, Air, & Soil Pollution, 2026)

EVs from Stem Cells Improve Mitochondrial Dysfunction in Neuronal Disorders - Sadaf Jahan; Dipak Kumar; Shaheen Ali; Arif Jamal Siddiqui; Mohammed Alaidarous; Johra Khan; Andleeb Khan (Molecular Neurobiology, 2026)

Lipopolysaccharide of Klebseilla pneumoniae as a potential vaccine target: extraction, purification and structural insights - Iram Murtaza; Sadaf Bashir; Imran Altaf; Rasheeda Bashir; Najiya al-Arifa; Kunza Latif (Folia Microbiologica, 2025)

Synergistic effects of selected ethnomedicinal plants with Metronidazole against resistant H. Pylori, and their urease inhibition mechanism - Sania Atta; Marya Nawaz Malik; Muhammad Tahir Aqeel; Iffat Naz; Nadeem Irshad; Sadaf Naz; Nadeem ul Hassan Khan; Faisal Rasheed; Humaira Fatima (South African Journal of Botany, 2025)

Nanoparticle-mediated modulation of microalgae to heavy metal co-exposure stress: A meta-analysis - Yan Li; Zhen Yu; Yifan Cui; Sadaf-Ilyas Kayani; Xianhui Xue; Xinjuan Hu; Jingya Qian; Feifei Zhu; Shuhao Huo (Journal of Hazardous Materials, 2025)

Bifunctional α-MnO2/NiFe-LDH composite electrode for highly efficient synergistic electrochemical arsenic remediation - Song Peng; Tiantian Wang; Sadaf Zulfiqar; Yang Wang (Chemical Engineering Journal, 2025)

Phenotypic Characterization and Adaptability of Wild Sugarcane to Diverse Pedospheric and Atmospheric Conditions - Ummar Iqbal; Mehboob Ahmad; Muhammad Sharif; Abdul Wahab; Muhammad Yousuf; Sadaf Rafiq; Sana Abid (Tropical Plant Biology, 2025)

Strengthening the Pediatric Radiation Oncology Workforce Through Digital Learning: A Capacity-Building Pilot from Pakistan - Bilal Mazhar Qureshi; Mariam Hina; Maheen Zakaria; Maria Tariq; Tooba Ali; Sadaf Altaf (Journal of Cancer Education, 2025)

Targeting the alpha-synuclein protein to treat Parkinson's disease using novel inhibitors identified using an integrated computational drug development approaches - Arif Jamal Siddiqui; Sadaf Jahan; Juhi Saxena; Manojkumar Sachidanandan; Riadh Badraoui; Mohd Adnan (In Silico Pharmacology, 2025)

Synergistic effect of carbon nanotubes decorated spinel ferrites nanocomposite for robust photocatalytic degradation of persistent environmental pollutants - Sadaf Fatima; Bushra Shaheen; Norah Alomayrah; Noor ul Ain; Muhammad Ibrar; Muhammad Farooq Warsi; Imran Shakir (Journal of Water Process Engineering, 2025)

Estimating digital adaptation and governance in international businesses by targeting environmental sustainability - Marco De Sisto; Shajara Ul-Durar; Noman Arshed; Ashina Sadaf; Alireza Nazarian (Journal of Environmental Management, 2025)

Jasmonates regulate metabolic cascade towards Eicosapentaenoic acid and Docosahexaenoic acid biosynthesis in filamentous microalga Tribonema minus - Sadaf-Ilyas Kayani; Feifei Zhu; Zhen Yu; Obaid Ur Rehman; Cunsheng Zhang; Muhammad Abdur Rehman Shah; Yan Li; Shuhao Huo (Bioresource Technology, 2025)

From scorching sands to survival: adaptive tale of the genus Tribulus (T. longipetalus, T. terrestris and T. pentandrus) in desert ecosystem - Ummar Iqbal; Muhammad Sharif; Sana Abid; Sadaf Rafiq; Abdul Wahab (The Science of Nature, 2025)

Reducing lead toxicity with advanced nanotechnology methods - Alireza Ghassemi Toussi; Sadaf Sadat Rafati; Elham Einafshar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Kaempferol alleviates cypermethrin induced reproductive toxicity in rats via Nrf2-mediated antioxidant and apoptotic regulation with histopathological evidence: in vivo and in silico study - Fahad Kabeer; Shaista Anjum; Atique Ahmed Behan; Muhammad Usman; Nazima Yousaf khan; Muhammad Azeem; Hafiz Misbah Ud Din; Muhammad Adeel Arshad; Sadaf Nazir; Shiping Cheng; Jameel Ahmed Buzdar (Journal of Molecular Histology, 2025)

Current status of technological advancement of ultrasound processing in the food industry and its SWOT analysis - Gazia Nasir; Sadaf Zaidi; Sameer Ahmad; Asfaq; Farhana Mehraj Allai; Faizan Ahmad; Ayon Tarafdar (Critical Reviews in Food Science and Nutrition, 2025)

Accelerated Chemical Space Generation of High Molar Extinction Organic Sensitizers via Machine Learning - Sadaf Noreen; Mamduh J. Aljaafreh (Journal of Fluorescence, 2025)

Exploring the Significance of β-glucan in Grains of Hulless Barley - Rizwan Ali Kumbhar; Kehan Yang; Shah Nawaz Mari Baloch; Sadaf Memon; Yajie Liu; Hui Zhao; Zongyun Feng (Plant Molecular Biology Reporter, 2025)

MAPK signaling mediates tamoxifen resistance in estrogen receptor-positive breast cancer - Sepide Javankiani; Soheil Bolandi; Anvar Soleimani; Mohammad Saeed Soleimani Meigoli; Mahdis Parsafar; Sadaf Safaei; Mojgan Esmailpour; Sogol Nadimi; Nahal Aghajamal Avval; Seyed Mohammad Ali Fazayel; Zahra Zahed; Malihe Sharafi (Molecular and Cellular Biochemistry, 2025)

Fertilizing Effects of Ulva intestinalis Derived Bio-Stimulant Enhance Spinacea oleracea L. Production, Nutrient Fluxes and Secondary Metabolism Under NaCl Stress - Sadaf Gul; Hamad Aslam; Muhammad Farrakh Nawaz; Ghulam Yasin; Sana Riaz; Maria Hasnain; Mohamed A. El-Sheikh; Emanuele Radicetti; Zainul Abideen (Journal of Soil Science and Plant Nutrition, 2025)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Predicting Stokes Shifts of Fluorescent Chromophores Using Ensemble Learning and H2OAutoML - Mamduh J. Aljaafreh; Sajjad H. Sumrra; Sadaf Noreen (Journal of Fluorescence, 2025)

Machine learning-driven prediction of Visual Range under changing climate conditions over complex terrain using AOD and CMIP6 climate simulations - Sadaf Javed; Muhammad Imran Shahzad; Muhammad Zeeshaan Shahid; Jun Wang; Imran Shahid (Remote Sensing Applications: Society and Environment, 2025)

Repurposing ivermectin: a new hope for glioblastoma multiforme? - Elmira Mohtashami; Bahram Bibak; Mehdi Sanati; Sadaf Afshari; Kolsoum Rezaie Kahkhaie; Mohammad Mahdi Vahedi; Mohammad Jalili-Nik; Amir R. Afshari; Sercan Karav; Tannaz Jamialahmadi; Amirhossein Sahebkar (Medicinal Chemistry Research, 2025)

Foliar Application of Ascorbic Acid and α-Tocopherol Enhances Salinity Tolerance in Hordeum vulgare L. by Regulating Antioxidant Enzymatic Activity and Improving Physiological and Biochemical Responses - Sadaf; Sami Ullah; Sikandar Shah; Aftab Jamal; Adil Mihoub; Muhammad Farhan Saeed; Iftikhar Ahmad; Emanuele Radicetti; Adil Zia; Andrea Mastinu; Jakub Černý (Journal of Crop Health, 2025)
Soil salinity severely impairs crop productivity by disrupting physiological and biochemical processes. This study investigated the efficacy of foliar-applied ascorbic acid (AsA) and α‑tocopherol (α-toc) in enhancing salinity tolerance in barley ( Hordeum vulgare L. cv. AJJ). A pot experiment using a randomized complete block design with three replicates was conducted under controlled conditions. Seedlings at the 4–5 leaf stage were exposed to 0, 40, or 80 mM NaCl salinity stress, followed by foliar treatments of AsA and α‑toc (150 mg L⁻ 1 ). Germination, agronomic, physiological, and biochemical parameters were analyzed. Salinity stress at 40 and 80 mM NaCl significantly reduced germination percentage (GP) by 18.6% and 18.4%, respectively, compared to the control (86.6%). Foliar application of AsA + α-toc under 40 and 80 mM stress restored GP to 82.3% and 81.7%, reflecting recoveries of 16.8% and 15.6% overstressed groups. Water content in leaves, shoots, and roots declined by 10–30% under salinity but improved by 15–25% with AsA + α-toc. Photosynthetic pigments were severely affected: chlorophyll a and total chlorophyll content (TCC) decreased by 45.7% (1.75 to 0.95 mg g⁻ 1 FW) and 10.9% (1.75 to 1.56 mg g⁻ 1 FW) at 40 and 80 mM NaCl, respectively. AsA + α-toc mitigated these losses, elevating TCC by 42.6% under 80 mM stress. Soluble protein content increased by 186% (0.50 to 1.43 mg g⁻ 1 ) under 80 mM stress but was stabilized by antioxidant treatments. Antioxidant enzymes, including superoxide dismutase (SOD) and peroxidase (POD), surged by 40–60% under salinity, while AsA + α-toc reduced hydrogen peroxide (H 2 O 2 ) and malondialdehyde (MDA) levels by 30–50%. The combined application of AsA and α‑toc proved most effective, enhancing stress tolerance through improved osmotic regulation, antioxidant defense, and chlorophyll preservation. These findings highlight the potential of AsA and α‑toc as sustainable agronomic tools for cultivating barley in saline soils, with AsA showing marginally greater efficacy. Further field studies are warranted to validate these results under different climatic conditions.

Protein sparing by dietary lipids in the diets of Pangasianodon hypophthalmus: an appraisal of growth, body composition, digestive enzymes, and metabolic responses - Sadaf Khadim; Mahroze Fatima; Syed Zakir Hussain Shah; Hamda Azmat; Muhammad Afzal Rashid (Fish Physiology and Biochemistry, 2025)

Anthropogenic dust pollution influences leaf and root morpho-anatomical traits by altering the metabolism and biochemical properties of indigenous vegetation - Muhammad Asim Sultan; Iftikhar Ahmad; Muhammad Arif; Saima Sadaf; Muhammad Kamran; Toqeer Abbas; Shifa Shaffique; Mansour K. Gatasheh (Environmental Geochemistry and Health, 2025)

Finding the Best Growth Media for Kiwifruit Cv. ‘Hayward’ Seedling Rootstocks in Mansehra District, Pakistan - Sadaf Bibi; Aftab Afzal; Ghulam Mujtaba Shah; Abdul Waheed; Muhammad Anas; Waseem Ahmed Khattak; Shah Fahad (Applied Fruit Science, 2025)

Determination of heavy metals and morphoanatomical characteristics of the monocots Aristida mutabilis and Cenchrus ciliaris in the dust-contaminated stone crushing industry of Sargodha, Pakistan - Muhammad Asim Sultan; Iftikhar Ahmad; Muhammad Arif; Saud Alamri; Manzer H Siddiqui; Saima Sadaf; Muhammd Kamran (Environmental Monitoring and Assessment, 2025)

Exploring single-atom catalysis for hydrogen evolution and storage: A DFT insight into first-row transition metal-porphyrin complexes (Porph@TMs) - Faheem Abbas; Saleem Nawaz Khan; Sadaf Bibi; Mariyum Yousaf; Francis Enujekwu; Muhammad Salman Khan; Sami Ullah; Mohammed Ali Assiri (Gas Science and Engineering, 2025)

Photocatalytic and photoelectrochemical H2 generation for sustainable future: Performance improvement, techno-economic analysis, and life cycle assessment for shaping the reality - Musfekur Rahman Dihan; Tanzim Ur Rahman; Md.Atquj Jaman Riad Khan; Tabassum Sunjida Banhi; Shoumik Sadaf; Md Sumon Reza; Shammya Afroze; Syed Z. Islam; Md.Shahinoor Islam (Fuel, 2025)

Unveiling the efficacy of TiO2-mediated calcareous nanocatalyst towards cost-effective biodiesel synthesis - Rashid Imran Ahmad Khan; D. Rhithuparna; Abdul Razzaq Khan; Sadaf Ahmad; Samuel Lalthazuala Rokhum; Gopinath Halder (Biomass and Bioenergy, 2025)

Structural Traits Driving Water Hyacinth (Eichhornia crassipes) Aggressive Spread and Ecosystem Disruption - Ummar Iqbal; Abdul Wahab; Sadaf Rafiq; Sibgha Noreen; Sana Abid; Muhammad Sharif; Mehboob Ahmad; Muhammad Yousuf (Water, Air, & Soil Pollution, 2025)

Alleviating cadmium-induced stress in maize: the role of zinc sulphate application on growth and biochemical responses - Sadaf Saeed; Awais Manzoor; Arslan Haider; Tahrim Ramzan; Hafeez ur Rehman; Muhammad Ahmad; Shahzad Bashir; Usman Zulfiqar; Muhammad Nazim; Muhammad Faisal Maqsood; Waleed A. A. Alsakkaf; Hayssam M. Ali (Environmental Science and Pollution Research, 2025)

Melanin: Comprehensive Insights into Pathways and Sustainable Applications - Ravinder Singh; Sadaf Rahman; Syed Ali Abbas; Amandeep Singh; Uzma Rahman; Manu Sharma; Nahida Rehman Mir; Nitika Kapoor; Noble K. Kurian (Current Pharmacology Reports, 2025)

Epidemiology and genetic characterization of Alternaria alternata causing leaf spot in Fragaria × ananassa - Nasir Mehmood; Abid Riaz; Salman Ghuffar; Sadaf Anwaar; Nyla Jabeen; Isha Shaheen; Muhammad Qasim; Salma Saeed Khan; Muhammad Rauf; Tauseef Anwar; Huma Qureshi; Ghadah Salim Abusalim; et al. (Fungal Biology, 2025)

Cobalt iron oxide nanorods with multi functions: solvothermal synthesis and characterizations as potent antimicrobial agent and photocatalyst - Bushra Uzair; Zukhra Abbasi; Basma Gul; Zulqurnain Ali; Khuram Shahzad; Sadaf Mushtaq; Farid Menaa (Environmental Nanotechnology, Monitoring & Management, 2025)

Silver Nanoparticles Derived from Probiotic Lactobacillus casei—a Novel Approach for Combating Bacterial Infections and Cancer - Arif Jamal Siddiqui; Mitesh Patel; Sadaf Jahan; Abdelmushin Abdelgadir; Mohammad Jahoor Alam; Mohammed Merae Alshahrani; Wael Alturaiki; Manojkumar Sachidanandan; Andleeb Khan; Riadh Badraoui; Mohd Adnan (Probiotics and Antimicrobial Proteins, 2025)

Neuroprotective effect of niacin in a rat model of obesity induced by high-fat-rich diet - Natasha Manzoor; Noreen Samad; Sheraz Ahmed Bhatti; Ali Irfan; Sadaf Ahmad; Gamal A. Shazly; Yousef A. Bin Jardan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Characteristics of aerosols and planetary boundary layer dynamics during biomass burning season - Muhammad Zeeshaan Shahid; Muhammad Imran Shahzad; Sundas Jaweria; Sadaf Javed; Shah Zaib; Imran Shahid (Natural Hazards, 2025)
The northeastern region of Pakistan (NEP) has experienced increased haze episodes over the past decade, primarily due to enhanced biomass burning activities during the post-monsoon season. Economic growth, urbanization and industrial development also controbuted to high pollutants levels that leads to decline in air quality and visibility. These elevated pollution levels over NEP (69–75.5°E, 27.4–34°N) are influenced by both meteorological conditions and anthropogenic activities. This study investigates aerosol concentrations before, during, and after the haze episode during November 2021 using model simulations and remote sensing data. The Modern-Era Retrospective Analysis for Research and Applications, version 2 (MERRA-2), along with satellite observations from the Moderate Resolution Imaging Spectroradiometer (MODIS), are used for validation and analysis of this haze episode. The results illustrate the key contributors to this haze event and showed the there is significant increases in aerosol components such as sulfate, black carbon, organic carbon, dust and aerosol optical depth (AOD). The planetary boundary layer (PBL) height, measured with Ceilometer LIDAR, showed decreasing trend in height from October to December that support aerosol accumulation near the surface during the the month of November. This month is also biomass burning, crop residue burning, season in the region. These haze episodes also impacts the atmospheric visibility that dropped below 2 km in November. These findings provide key insights into the complex interactions between meteorology, emissions, and haze formation in NEP region, and will provide policy makers to design effective mittigation strategies.

Biochar and Pseudomonas aeruginosa M2 Co-Application: A Sustainable Strategy for Enhancing Growth and Heavy Metal Tolerance in Brassica campestris - Muhammad Muzammil Mukhtar; Qasim Ali; Muhaimen Ayyub; Muhammad Aon; Hayssam M. Ali; Sadaf Oranab; Iftikhar Ahmad; Ghulam Abbas; Behzad Murtaza; Waqas Mohy-Ud-Din; Usman Zulfiqar; Muhammad Faisal Maqsood; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Exploring New Azobenzene Type Photoswitches by Machine Learning with Lowest Possible Fluorescence Excitons with Ease of Synthesis - Azal S. Waheeb; Duha M. Hasan; Shaimaa H. Mallah; Sajjad H. Sumrra; Sadaf Noreen; Ashraf Y. Elnaggar; Abrar U. Hassan; Islam H. El Azab; Hussein A. K. Kyhoiesh; Mohamed H. H. Mahmoud (Journal of Fluorescence, 2025)

Improved charge carrier dynamics in rationally designed F-g-C3N4/In2O3 type II heterojunction for efficient pollutant removal: Mechanistic insights, real-world applications, and toxicity study - Arun S. Chopade; Akshay A. Ransing; Vinayak G. Parale; Santosh V. Mohite; Abhijit N. Kadam; Jiseung Kim; Vaishali A. Patil; Sadaf Jamal Gilani; Mohaseen S. Tamboli; Hyun-Kyung Kim; Dattakumar S. Mhamane; Hyung-Ho Park; et al. (Journal of Water Process Engineering, 2025)

Postharvest quality assessment of tomato during storage: An experimental and ML fusion - Rameez Ahmad Aftab; Faizan Ahmad; Mohd Monish; Sadaf Zaidi (Journal of Stored Products Research, 2025)

A study on enhanced mechanical properties of wood in the parallel-to-grain direction in timber-filled-steel tubular columns - Sadaf Karkoodi; Hassan Karampour; Benoit P. Gilbert; Shanmuganathan Gunalan (Engineering Structures, 2025)

Innovative early age mechanical properties of 3D printable mortar enhanced with SBR latex and kaolin - Mazhar Yasin; Zahid Ahmad Siddiqi; Atteq Ur Rehman; Sadaf Noshin; Hafiz Muhammad Shahzad Aslam (European Journal of Environmental and Civil Engineering, 2025)

Response surface optimization for biodiesel production from chicken fat via transesterification process over CaO-CeO2 catalyst - Hifza Rouf; Rehana Kousar; Zia Ul Haq; Syed Muhammad Wajahat ul Hasnain; Sajjad Haider; Salahuddin Khan; Sadaf Ul Hassan (Sustainable Chemistry and Pharmacy, 2025)

A Review on Treatment Methods, Recycling, and Reuse of Ablution Greywater for Sustainable Water Resource Management - Sadaf Tagar; Naveed Ahmed Qambrani (Water Conservation Science and Engineering, 2025)

Bacillus subtilis (NMCC-path-14) ameliorates acute phase of arthritis via modulating NF-κB and Nrf-2 signaling in mice model - Muhammad Usama Mazhar; Sadaf Naz; Tayyaba Zulfiqar; Jehan Zeb Khan; Fahim Hilal; Shakira Ghazanfar; Muhammad Khalid Tipu (Inflammopharmacology, 2025)

Comparative Analysis of Heavy Metals and Minerals in Dairy and Plant-Based Milk Alternatives Available in Pakistan’s Markets - Aiman Usman; Sadaf Yaqoob; Hamza Shafiq; Mamoona Amir; Muhammad Riaz; Kousar Parveen; Usama Usman (Biological Trace Element Research, 2025)

Thriving in extremes: Adaptability potential of desert cotton Aerva javanica to hyper-arid saline conditions - Ummar Iqbal; Sana Abid; Muhammad Sharif; Sadaf Rafiq; Abdul Wahab; Mehboob Ahmad; Muhammad Yousuf (Journal of Arid Environments, 2025)

Phytoremediation Capacity of Saltwort (Salsola imbricata Forssk.) Determined by Tissue Organization and Physio-biochemical traits under Arid Saline Environments - Ummar Iqbal; Muhammad Sharjeel Arif; Muhammad Sharif; Abdul Wahab; Mehboob Ahmad; Muhammad Yousuf; Sadaf Rafiq; Sana Abid (Water, Air, & Soil Pollution, 2025)

Exploring ultraviolet and nitrous acid-induced mutagenesis of Rhizopus oligosporus for extracellular inulinase production under solid-state culture - Syeda Wajiha Khalid; Sikander Ali; Sadaf Mutahir; Muhammad Asim Khan; Abdulrahman A. Almehizia; Jahangir Khan; Amna Waseem (Brazilian Journal of Microbiology, 2025)

Multifunctional performance of chitosan/soy protein isolation-based films impregnated carbon dots/anthocyanin derived from purple hull pistachio for tracking and extending the shelf life of fish - Sepideh Hadavifar; Reza Abedi-Firoozjah; Behnam Bahramian; Nasim Jafari; Sadaf Mohajjel Sadeghi; Sahar Majnouni; Behzad Ebrahimi; Ali Ehsani; Milad Tavassoli (Food Hydrocolloids, 2025)

Impregnation of granular activated carbon with nickel or copper improves performance of microbial electrosynthesis - Igor Vassilev; Hui Yao; Sadaf Shakeel; Markus Tuominen; Anne Heponiemi; Davide Bergna; Ulla Lassi; Marika Kokko (Bioresource Technology, 2025)

A DNase from halophilic bacterium Bacillus pacificus targets two notorious biofilms of Pseudomonas aeruginosa PAO1 and Staphylococcus aureus - Sadaf Salim; Vusqa Jadoon; Mugheesa Batool; Irfan Ali; Usman Irshad; Raza Ahmed; Sadaf Qayyum; Awal Noor; Tatheer Alam Naqvi (Biocatalysis and Agricultural Biotechnology, 2025)

Surface Water Analysis for Physical Parameters, Fecal Indicator Bacteria, and Identification of the Origin of Contamination - Sadaf Tagar; Naveed Ahmed Qambrani; Zubair Ahmed; Kamran Ansari; Rasool Bux Mahar; Muhammad Muqeet; Syed Muhammad Zaki Zaidi (Water, Air, & Soil Pollution, 2025)

The effects of ursodeoxycholic acid on Parkinson’s disease, a mechanistic review of the recent evidence - Seyed Mehrad Razavi; Niusha Esmaealzadeh; Mazyar Ataei; Nadia Afshari; Moloud Saleh; Yasaman Amini; Sadaf Hasrati; Fatemeh Ghazizadeh Hashemi; Abolghasem Mortazavi; Leila Mohaghegh Shalmani; Amir Hossein Abdolghaffari (Metabolic Brain Disease, 2025)

Endometrioid tubal intraepithelial neoplasia (E-TIN): case report & literature review - Sadaf Muzaffar; Shireen R. Abdullah (Journal of Molecular Histology, 2025)

Cyclosporin for the treatment of Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN): a systematic review of observational studies and clinical trials focusing on single therapy, combination therapy, and comparative assessments - Amirhossein Nazerian; Alireza Jafarzadeh; Sadaf Salehi; Mobina Ghasemi; Azadeh Goodarzi (Inflammopharmacology, 2025)

Palyno-anatomical diversity and its implication in the taxonomy of some Plantaginaceae species - Maryam Akram Butt; Nafeesa Zahid; Saraj Bahadur; Sadaf Kayani; Javeed Hussain; Muhammad Zafar (Genetic Resources and Crop Evolution, 2025)

Machine Learning Assisted Bithiophene Based Donor Acceptor Selection to Design New Fluoresent Dyes for Photovoltaic Applications - Sadaf Noreen; Sajjad H. Sumrra; Abrar U. Hassan; Ayesha Mohyuddin; Hussein A. K. Kyhoiesh; Ashraf Y. Elnaggar; Islam H. El Azab; Mohamed H. H. Mahmoud (Journal of Fluorescence, 2025)

Decontamination of fish aquarium wastewater by ozonation catalyzed by multi-metal loaded activated carbons for sustainable aquaculture - Amir Ikhlaq; Mamoona Kanwal; Osama Shaheen Rizvi; Naveed Ramzan; Asia Akram; Umair Yaqub Qazi; Fei Qi; Sadaf Ul Hassan; Rahat Javaid (Process Safety and Environmental Protection, 2025)

Text-based algorithms for automating life cycle inventory analysis in building sector life cycle assessment studies - Sadaf Gachkar; Darya Gachkar; Erfan Ghofrani; Antonio García Martínez; Cecilio Angulo Bahón (Journal of Cleaner Production, 2025)

Abundance and distribution of anthropogenic marine litter on the beaches of Sonadia Island: An Ecologically Critical Area - Masum Howlader; Shah Newaz Alam Shuvo; Abu Selim; Md Monirul Islam; Molla Rahman Shaibur; Sabiha Sarwar; Jehan Y. Al-Humaidi; Raed H. Althomali; Sumaiya Sadaf; Mehedi Hasan; Md. Sabit Mia; Mohammad Moniruzzaman; et al. (Regional Studies in Marine Science, 2024)

Sustainable electrocoagulation for lignin valorization: Green synthesis of magnetic mesoporous activated carbon from pulp and paper industry black liquor and its application as an adsorbent for methylene blue - Shoumik Sadaf; Seyed Morteza Taghavi Kouzehkanan; Tae-Sik Oh; Zhihua Jiang (Journal of Water Process Engineering, 2024)

Wood biochar induced metal tolerance in Maize (Zea mays L.) plants under heavy metal stress - Atiqa Zahra; Sadaf Kayani; Asim Shahzad; Tijen Demiral Sert; Hasan Ozcelik; Mingzhou Qin; Muhammad Naeem; Motsim Billah (Environmental Research, 2024)

Photoprotective and bioinspired cerium-encapsulating lignin nanocapsules for multifunctional UV protection applications - Sadaf Mearaj; Tae Min Kim; Joon Weon Choi (Chemical Engineering Journal, 2024)

Liquid biopsy for CNS lymphoma: CSF exosomes and CSF exosomal miR-15a, miR-21, miR-155, miR-210, and miR-19b are promising biomarkers for diagnosis - Mustafa Aziz Hatiboglu; Busra Karacam; Imran Khan; Kerime Akdur; Elif Burce Elbasan; Sadaf Mahfooz; Mehmet Hakan Seyithanoglu; Guven Cetin; Meliha Gundag Papaker; Mustafa Namik Oztanir (Molecular Biology Reports, 2024)

Nitrogen and carbohydrate metabolisms are key factors in maize (Zea mays L.) germination under chromium-induced ROS - Muhammad Imran Atta; Syeda Sadaf Zehra; Zhihang Zhuo; Habib Ali; Malik Waseem Abbas; Syed Naveed Abbas; Sadia Sarwar; Fatima Muneer; Irfan Ahmad; Danpping Xu; Hasham S. Almoallim; Mohammad Javed Ansari (Journal of Plant Diseases and Protection, 2024)

Integrating HRMAS-NMR Data and Machine Learning-Assisted Profiling of Metabolite Fluxes to Classify Low- and High-Grade Gliomas - Safia Firdous; Zubair Nawaz; Rizwan Abid; Leo L. Cheng; Syed Ghulam Musharraf; Saima Sadaf (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Can nanotechnology and genomics innovations trigger agricultural revolution and sustainable development? - Arzish Javaid; Sadaf Hameed; Lijie Li; Zhiyong Zhang; Baohong Zhang; Mehboob-ur -Rahman (Functional & Integrative Genomics, 2024)
At the dawn of new millennium, policy makers and researchers focused on sustainable agricultural growth, aiming for food security and enhanced food quality. Several emerging scientific innovations hold the promise to meet the future challenges. Nanotechnology presents a promising avenue to tackle the diverse challenges in agriculture. By leveraging nanomaterials, including nano fertilizers, pesticides, and sensors, it provides targeted delivery methods, enhancing efficacy in both crop production and protection. This integration of nanotechnology with agriculture introduces innovations like disease diagnostics, improved nutrient uptake in plants, and advanced delivery systems for agrochemicals. These precision-based approaches not only optimize resource utilization but also reduce environmental impact, aligning well with sustainability objectives. Concurrently, genetic innovations, including genome editing and advanced breeding techniques, enable the development of crops with improved yield, resilience, and nutritional content. The emergence of precision gene-editing technologies, exemplified by CRISPR/Cas9, can transform the realm of genetic modification and enabled precise manipulation of plant genomes while avoiding the incorporation of external DNAs. Integration of nanotechnology and genetic innovations in agriculture presents a transformative approach. Leveraging nanoparticles for targeted genetic modifications, nanosensors for early plant health monitoring, and precision nanomaterials for controlled delivery of inputs offers a sustainable pathway towards enhanced crop productivity, resource efficiency, and food safety throughout the agricultural lifecycle. This comprehensive review outlines the pivotal role of nanotechnology in precision agriculture, emphasizing soil health improvement, stress resilience against biotic and abiotic factors, environmental sustainability, and genetic engineering.

Therapeutic Potential of Green Synthesized Silver Nanoparticles for Promoting Wound-Healing Process in Diabetic Mice - Riffat Iqbal; Amna Asghar; Arslan Habib; Shaista Ali; Sadaf Zahra; Muhammad Imran Hussain; Ahmad Bilal Ahsan; Yulai Liang (Biological Trace Element Research, 2024)

Recent development towards the novel applications and future prospects for cellulose-metal organic framework hybrid materials: a review - Zeenat Qamar; Awais Ali Aslam; Farheen Fatima; Sadaf Ul Hassan; Muhammad Shahid Nazir; Zulfiqar Ali; Sameer Ahmed Awad; Aqeel Ahmad Khan (Environmental Science and Pollution Research, 2024)

Bombyx mori serpin 3 is involved in innate immunity by interacting with serine protease 7 to regulate prophenoloxidase activation - Hui-Hua Cao; Yu-Ling Wang; Shahzad Toufeeq; Wei-Wei Kong; Sadaf Ayaz; Shi-Huo Liu; Jie Wang; Jia-Ping Xu (Journal of Invertebrate Pathology, 2024)

Evaluating the impact of data pre-processing methods on classification of ATR-FTIR spectra of bituminous binders - Sadaf Khalighi; Lili Ma; Shisong Ren; Aikaterini Varveri (Fuel, 2024)

Synthesis of green magnetic hybrid adsorbents and their application for reactive red methyl 4 BL dye removal - Sadaf Gillani; Ruba Munir; Khuram Ali; Muhammad Zeeshan Bashir; Umme Habibah Siddiqua; Saima Noreen (Clean Technologies and Environmental Policy, 2024)

Site-specific design response spectra proposed for Sarcheshmeh Copper Mine in Iran and seismic hazard analysis - Zahra Sabzi; Sadaf Dalirazar (Arabian Journal of Geosciences, 2024)

Retraction Note: Measuring technical efficiency associated with environmental investment: does market competition and risk matters in banking sector - Supat Chupradit; Dai Yannan; Hafiz Waqas Kamran; Sadaf S. Soudagar; Alaa Mohamd Shoukry; Jameel A. Khader (Environmental Science and Pollution Research, 2024)

Chlorogenic Acid Enhances the Chaperone Potential of BSA at Physiological Concentrations on Model Protein Cytochrome c - Sadaf Khan; Neha Kausar Ansari; Aabgeena Naeem (Cell Biochemistry and Biophysics, 2024)

Maximizing the wetting resistance of fluorine-free omniphobic membranes for hypersaline wastewater desalination - Yinchuan Yang; Sifat Kalam; Sadaf Shabanian; Kevin Golovin; Xuefei Zhou; Yalei Zhang; Jongho Lee (Water Research, 2024)

Mechanistic insights into the nutritional and therapeutic potential of Spirulina (Arthrospira) spp.: Challenges and opportunities - Muhammad Abdur Rehman Shah; Feifei Zhu; Yi Cui; Xinjuan Hu; Huayou Chen; Sadaf-Ilyas Kayani; Shuhao Huo (Trends in Food Science & Technology, 2024)

A data-driven approach to quantify track buckling strength through the development and application of a Track Strength Index (TSI) - Sadaf Shafie Zadeh A.; J. Riley Edwards; Arthur de O. Lima; Marcus S. Dersch; Paula Palma (Transportation Geotechnics, 2024)

A bibliographic analysis of optimization of hydrogen production via electrochemical method using machine learning - Sadaf Iqbal; Kiran Aftab; Fakiha tul Jannat; Muhammad Ali Baig; Umme Kalsoom (Fuel, 2024)

Unveiling the nexus between atmospheric visibility, remotely sensed pollutants, and climatic variables across diverse topographies: A data-driven exploration empowered by artificial intelligence - Sadaf Javed; Muhammad Imran Shahzad; Imran Shahid (Atmospheric Pollution Research, 2024)

Elucidation of SSR polymorphism in human pathogenic fungi Cryptococcus neoformans with focus on isolate-specific marker generation and genetic diversity assessment - Malik Asif Hussain; Jitendra Narayan; Anil Kumar Dwivedi; Nuha Abdel Rahman Khalil Mohammed; Mohd Adnan Kausar; Sadaf Anwar; Rajeev Singh; Amany Mohammed Khalifa; Sahil Mahfooz (Biologia, 2024)

In vivo evaluation of efficacy and safety of Coagulansin-A in treating arthritis - Sadaf Naz; Muhammad Usama Mazhar; Sidra Faiz; Maria Nawaz Malik; Jehan Zeb Khan; Ihsan Ul Haq; Lin Zhu; Muhammad Khalid Tipu (Toxicology and Applied Pharmacology, 2024)

Nature-based solutions as buffers against coastal compound flooding: Exploring potential framework for process-based modeling of hazard mitigation - Soheil Radfar; Sadaf Mahmoudi; Hamed Moftakhari; Trevor Meckley; Matthew V. Bilskie; Renee Collini; Karim Alizad; Julia A. Cherry; Hamid Moradkhani (Science of The Total Environment, 2024)

Modeling green energy and innovation for ecological risk management using second generation dynamic quantile panel data model - Shajara Ul-Durar; Noman Arshed; Marco De Sisto; Alireza Nazarian; Ashina Sadaf (Journal of Environmental Management, 2024)

Advanced AI approach for enhanced predictive modeling in reservoir characterization within complex geological environments - Wakeel Hussain; Muhammad Ali; Rakhshanda Sadaf; Harith F. Al-Khafaji; Izhar Sadiq; Chuanyu Hu; Hamza Daud; Salah Alshareef Alkfakey Ahmed (Modeling Earth Systems and Environment, 2024)

Correction: Unraveling the Role of Plant Growth Regulators and Plant Growth Promoting Rhizobacteria in Phytoremediation - Sadaf Jan; Renu Bhardwaj; Neeta Raj Sharma; Rattandeep Singh (Journal of Plant Growth Regulation, 2024)

Unraveling the Role of Plant Growth Regulators and Plant Growth Promoting Rhizobacteria in Phytoremediation - Sadaf Jan; Renu Bhardwaj; Neeta Raj Sharma; Rattandeep Singh (Journal of Plant Growth Regulation, 2024)

High-throughput digital imaging analysis for grain morphology of historical wheat cultivars of Pakistan - Tehreem Tahir; Awais Rasheed; Sadaf Kayani; Asim Shahzad (Genetic Resources and Crop Evolution, 2024)

Innovative Approach to Characterize Cheese Whey Anaerobic Digestion Using Combined Mechanistic and Machine Learning Models - Md Tausif Akram; Rameez Ahmad Aftab; Khursheed B. Ansari; Iram Arman; Mohammad Abdul Hakeem; Sadaf Zaidi; Mohammad Danish (BioEnergy Research, 2024)

Effective antibacterial agents in modern wound dressings: a review - Sadaf Torabi; Sayed Ali Hassanzadeh-Tabrizi (Biofouling, 2024)

Dancing with danger-how honeybees are getting affected in the web of microplastics-a review - Sadaf Bashir; Pritha Ghosh; Priyanka Lal (NanoImpact, 2024)

Numerical Estimation of Surface Soil Moisture by Machine Learning Algorithms in Different Climatic Types - Sadaf Ahmadnejad; Mehdi Nadi; Pouya Aghelpour (Pure and Applied Geophysics, 2024)

Flood impact assessment on agricultural and municipal areas using Sentinel-1 and 2 satellite images (case study: Kermanshah province) - Sadaf Gord; Maryam Hafezparast Mavaddat; Rasool Ghobadian (Natural Hazards, 2024)

Correction: Shear Strength and Consolidation Behaviour of Kaolin Clay Reinforced with a Granular Column Backfilled with Crushed Waste Glass - Danish Kazmi; Mehdi Serati; David J. Williams; Sebastian Quintero Olaya; Sadaf Qasim; Yi Pik Cheng; Athina Grizi; Akbar A. Javadi (Geotechnical and Geological Engineering, 2024)

Shear Strength and Consolidation Behaviour of Kaolin Clay Reinforced with a Granular Column Backfilled with Crushed Waste Glass - Danish Kazmi; Mehdi Serati; David J. Williams; Sebastian Quintero Olaya; Sadaf Qasim; Yi Pik Cheng; Athina Grizi; Akbar A. Javadi (Geotechnical and Geological Engineering, 2024)
Granular columns are commonly used for ground improvement. However, minimal research is presently available on the effect of backfill particle size on the geotechnical performance of granular column-reinforced soil. Geo-environmentally, using crushed waste glass (CWG) as a sustainable replacement for depleting traditional construction sands could offer a cleaner feedstock to backfill granular columns while helping recycle growing stockpiles of waste glass, potentially supporting the circular economy transition and decarbonisation of the construction industry. Given these multi-pronged motivations, this study investigated the shear strength and consolidation behaviour of kaolin reinforced with a CWG granular column. Three different particle size ranges (PSR) of CWG were discretely used to install a granular column in the kaolin bed, including fine (0.50–1.0 mm), medium (1.0–1.7 mm) and coarse (1.7–3.35 mm) particles with median particle sizes of 0.78 mm, 1.42 mm and 2.30 mm, respectively. The geocomposite containing a medium CWG column showed the highest increase in friction angle, increasing from 14.0° for kaolin only specimens to 20.7° for the geocomposites. Similarly, the consolidation behaviour of reinforced kaolin (geocomposites) was typically superior to that of kaolin only specimens. Notably, installing a coarse, medium or fine CWG column decreased the average compression index (C c ) of the geocomposites by almost 17%, 35% or 50%, respectively, compared to that of the kaolin only specimens. Given the promising results of this initial study, some suggestions are provided for future studies on assessing the application of CWG as an alternative backfill and sustainable geomaterial in granular column construction. Video abstract This internationally-partnered Video Abstract highlights the findings of the research study, indicating that crushed waste glass (CWG) could potentially serve as a sustainable geomaterial and be used as a replacement for traditional construction sand to backfill granular columns in clayey soils for ground improvement, helping reduce the unsustainable exploitation of sand resources and increasing waste glass recycling, potentially supporting the paradigm shift to a circular economy and contributing to decarbonisation of the construction industry.

Antihypertensive effect of patulitrin and other constituents from Tagetes patula L. (French marigold) in acute L-NAME induced hypertensive rats - Farzana Sadaf; Rubeena Saleem; Rashid A. Khan; Usman Ahmad; Lubna; Samina Bano; Shaheen Faizi (Natural Product Research, 2024)

BmNPV p35 regulates apoptosis in Bombyx mori via a novel target of interaction with the BmVDAC2-BmRACK1 complex - Lin-Bao Zhu; Han-Dan Zhu; Zhi-Hao Huang; Hui-Hua Cao; Sadaf Ayaz; Jia-Yue Yang; Xi-Ya Chen; Ying Zhang; Shi-Huo Liu; Jia-Ping Xu (Insect Biochemistry and Molecular Biology, 2024)

The chemotrophic behaviour of Aspergillus niger: Mapping hyphal filaments during chemo-sensing; the first step towards directed materials formation - Ayesha Sadaf; Matthias Brock; Carole C. Perry (Fungal Biology, 2024)

Modelling and statistical interpretation of phenol adsorption behaviour of 3-Dimensional hybrid aerogel of waste-derived carbon nanotubes and graphene oxide - Marut Jain; Abhisek Sahoo; Deepti Mishra; Sadaf Aiman Khan; Kamal Kishore Pant; Zyta M. Ziora; Mark A.T. Blaskovich (Chemical Engineering Journal, 2024)

Fetal QRS extraction from single-channel abdominal ECG using adaptive improved permutation entropy - Nastaran Mansourian; Sadaf Sarafan; Farah Torkamani-Azar; Tadesse Ghirmai; Hung Cao (Physical and Engineering Sciences in Medicine, 2024)

Current perspectives and difficulties in the design of acaricides and repellents from plant-derived compounds for tick control - Nosheen Malak; Sadaf Niaz; Estefan Miranda-Miranda; Raquel Cossío-Bayúgar; Jonny Edward Duque; Itzel Amaro-Estrada; Nasreen Nasreen; Adil Khan; Joanna Kulisz; Zbigniew Zając (Experimental and Applied Acarology, 2024)

Ecological transitions in Xinjiang, China: Unraveling the impact of climate change on vegetation dynamics (1990–2020) - Haichao Hao; Junqiang Yao; Yaning Chen; Jianhua Xu; Zhi Li; Weili Duan; Sadaf Ismail; Guiling Wang (Journal of Geographical Sciences, 2024)

In silico and in vitro assessment of drugs potentially causing adverse effects by inhibiting CYP17A1 - Jacek Kędzierski; Marie-Christin Jäger; Sadaf Naeem; Alex Odermatt; Martin Smieško (Toxicology and Applied Pharmacology, 2024)

Rh/InGaN1−O nanoarchitecture for light-driven methane reforming with carbon dioxide toward syngas - Yixin Li; Jinglin Li; Tianqi Yu; Liang Qiu; Syed M. Najib Hasan; Lin Yao; Hu Pan; Shamsul Arafin; Sharif Md. Sadaf; Lei Zhu; Baowen Zhou (Science Bulletin, 2024)

Electrocoagulation-based wastewater treatment process and significance of anode materials for the overall improvement of the process: A critical review - Shoumik Sadaf; Hridoy Roy; Athkia Fariha; Tanzim Ur Rahman; Nishat Tasnim; Nusrat Jahan; Adewale Allen Sokan-Adeaga; Safwat M. Safwat; Md Shahinoor Islam (Journal of Water Process Engineering, 2024)

Source of arsenic pollution in southern Indus alluvial plain aquifers, Pakistan - Sadaf Naseem; Sanober Rafi (Groundwater for Sustainable Development, 2024)

Unlocking the interaction of organophosphorus pesticide residues with ecosystem: Toxicity and bioremediation - Sadaf Tanveer; Noshin Ilyas; Nosheen Akhtar; Nazish Akhtar; Nageen Bostan; Zuhair Hasnain; Abdullah Niaz; Gokhan Zengin; Abdul Gafur; Betty Natalie Fitriatin (Environmental Research, 2024)

Immunostimulant, hepatoprotective, and nephroprotective potential of Bacillus subtilis (NMCC-path-14) in comparison to dexamethasone in alleviating CFA-induced arthritis - Muhammad Usama Mazhar; Sadaf Naz; Tayyaba Zulfiqar; Jehan Zeb Khan; Shakira Ghazanfar; Muhammad Khalid Tipu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Photocatalytic degradation of parabens: A comprehensive meta-analysis investigating the environmental remediation potential of emerging pollutant - Sadaf Aiman Khan; Marut Jain; Kamal Kishore Pant; Zyta Maria Ziora; Mark A.T. Blaskovich (Science of The Total Environment, 2024)

Brown macro-seaweeds derived agro-biostimulant for Zea mays farming in saline conditions: Growth enhancement and optimum biochemical and ion feedback - Sadaf Gul; Muhammad Farrakh Nawaz; Muhammad Talha Bin Yousaf; Muhammad Haroon U Rashid; Muhammad Yousuf Adnan; Shamama Tausif; Arooj Javed; Zainul Abideen; Ali El- Keblawy (Biocatalysis and Agricultural Biotechnology, 2024)

Anti-inflammatory and anti-arthritic potential of Coagulansin-A: in vitro and in vivo studies - Sadaf Naz; Muhammad Usama Mazhar; Umakant Yadav; Hamdy Abouzeid Ali; Fadi Khasawneh; Ihsan-ul-Haq; Muhammad Khalid Tipu; Lin Zhu (Inflammopharmacology, 2024)

PKHD1L1, a gene involved in the stereocilia coat, causes autosomal recessive nonsyndromic hearing loss - Shelby E. Redfield; Pedro De-la-Torre; Mina Zamani; Hanjun Wang; Hina Khan; Tyler Morris; Gholamreza Shariati; Majid Karimi; Margaret A. Kenna; Go Hun Seo; Hongen Xu; Wei Lu; et al. (Human Genetics, 2024)
Identification of genes associated with nonsyndromic hearing loss is a crucial endeavor given the substantial number of individuals who remain without a diagnosis after even the most advanced genetic testing. PKHD1L1 was established as necessary for the formation of the cochlear hair-cell stereociliary coat and causes hearing loss in mice and zebrafish when mutated. We sought to determine if biallelic variants in PKHD1L1 also cause hearing loss in humans. Exome sequencing was performed on DNA of four families segregating autosomal recessive nonsyndromic sensorineural hearing loss. Compound heterozygous p.[(Gly129Ser)];p.[(Gly1314Val)] and p.[(Gly605Arg)];p[(Leu2818TyrfsTer5)], homozygous missense p.(His2479Gln) and nonsense p.(Arg3381Ter) variants were identified in PKHD1L1 that were predicted to be damaging using in silico pathogenicity prediction methods. In vitro functional analysis of two missense variants was performed using purified recombinant PKHD1L1 protein fragments. We then evaluated protein thermodynamic stability with and without the missense variants found in one of the families and performed a minigene splicing assay for another variant. In silico molecular modeling using AlphaFold2 and protein sequence alignment analysis were carried out to further explore potential variant effects on structure. In vitro functional assessment indicated that both engineered PKHD1L1 p.(Gly129Ser) and p.(Gly1314Val) mutant constructs significantly reduced the folding and structural stabilities of the expressed protein fragments, providing further evidence to support pathogenicity of these variants. Minigene assay of the c.1813G>A p.(Gly605Arg) variant, located at the boundary of exon 17, revealed exon skipping leading to an in-frame deletion of 48 amino acids. In silico molecular modeling exposed key structural features that might suggest PKHD1L1 protein destabilization. Multiple lines of evidence collectively associate PKHD1L1 with nonsyndromic mild–moderate to severe sensorineural hearing loss. PKHD1L1 testing in individuals with mild–moderate hearing loss may identify further affected families.

Modification of mechanical, rheological and structural properties of agar hydrogel using xanthan and locust bean gum - Faezeh Khoobbakht; Sadaf Khorshidi; Fereshte Bahmanyar; Seyede Marzieh Hosseini; Nafise Aminikhah; Mehdi Farhoodi; Leila Mirmoghtadaie (Food Hydrocolloids, 2024)

Beyond contamination: Enhancing plant tolerance to arsenic through phytobial remediation - Saeed ur Rahman; Xinxin Liu; Muhammad Khalid; Asad Rehman; Junfeng Cao; Sadaf-Ilyas Kayani; Muhammad Naeem; Naveed Ahmad; Abid Ali Khan; Muhammad Aamir Manzoor; Chang Zhao; Haoxin Tan; et al. (South African Journal of Botany, 2024)

Imiquimod as a new treatment in refractory idiopathic granulomatous mastitis: report of two cases - Sadaf Alipour; Bardia Gholami; Marzieh Orouji; Samareh Heydari (DARU Journal of Pharmaceutical Sciences, 2023)

Unlocking green innovation and environmental performance: the mediated moderation of green absorptive capacity and green innovation climate - Sadaf Akhtar; Cai Li; Jan Muhammad Sohu; Yasir Rasool; Muhammad Iatzaz Ul Hassan; Muhammad Bilal (Environmental Science and Pollution Research, 2023)

Characterization of gellan gum-chitosan based hydrogel to evaluate as a potential gelatin substitute - Sadaf Khorshidi; Faezeh Khoobbakht; Leila Mirmoghtadaie; Seyede Marzieh Hosseini (Food Hydrocolloids, 2023)

The influence of ultrasound-assisted osmotic dehydration as a pre-treatment method on the quality of vacuum dried pineapple - Faizan Ahmad; Sadaf Zaidi (Food and Humanity, 2023)

Genome-wide identification and expression analysis of U-box gene family in Juglans regia L. - Hanif Khan; Umar Zeb; Sadaf Gul; Azizullah Aziziullah; Naushad Ali; Sajid Fiaz; Asmaa M. Abushady; Shariat Ullah; Salar Muhammad; Kotb A. Attia; Itoh Kimiko; Fengjie Cui; et al. (Genetic Resources and Crop Evolution, 2023)

Genome-wide characterization and expression analysis of cyclic nucleotide-gated ion channels (CNGCs) gene family in Arabidopsis thaliana L. and Helianthus annuus L. for drought stress - Sadaf Oranab; Hafiz Muhammad Ahmad; Sajid Fiaz; Athar Hussain; Muhammad Rizwan; Shazia Arif; Saira Ishaq; Shahnaz Zakia; Asmaa M. Abushady; Itoh Kimiko; Kotb A. Attia (Brazilian Journal of Botany, 2023)

Shark fish oil prevents scopolamine-induced memory impairment in an experimental model - Sadaf Naeem; Liaquat Ali; Nazish Jaffar; Saira Saeed Khan; Yousra Shafiq; Sadia Suri; Anosh Tahir (Metabolic Brain Disease, 2023)

LC-ESI-MS analysis, antioxidant, anti-diabetic and molecular docking studies on Corchorus depressus (L.) C.Chr - Shazia Anjum; Humna Tahir; Sadia Sarwar; Wajid Raza; Irum Latif; Hafiz Muhammad Farhan Rasheed; Qaiser Jabeen; Wardah Shahid; Muhammad Ashraf; Syeda Sadaf Zehra; Zaheer Ul-Haq; Muhammad Ayaz; et al. (Natural Product Research, 2023)

The pesticide thiamethoxam induced toxicity in Brassica juncea and its detoxification by Pseudomonas putida through biochemical and molecular modifications - Sadaf Jan; Bhupender Singh; Renu Bhardwaj; Rattandeep Singh; Abdulaziz Abdullah Alsahli; Prashant Kaushik; Parvaiz Ahmad (Chemosphere, 2023)

A comprehensive study of the sources, extraction methods and structures of the Saponin compounds for its antidiabetic activity - Muhammad Umair Afzal; Muhammad Pervaiz; Anam Ejaz; Eisha Bajwa; Sadaf Naz; Zohaib Saeed; Sami Ullah; Syeda Shaista Gillani; Rana Rashad Mehmood Kan; Umer Younas (Biocatalysis and Agricultural Biotechnology, 2023)

Predictive modeling of earthquake vulnerability using geospatial data: a focus on Pakistan - Gohar Ali Mahar; Rakhshanda Sadaf; Noor Hussain Chandio (Arabian Journal of Geosciences, 2023)

Physical activity and obesity spectrum disorders in post-bariatric surgery patients: A systematic review and Meta-analysis - Amin Gasmi; Boukelia Boukhmis; Geir Bjørklund; Ibrahim H. Elkhidir; Yuliya Semenova; Alexandru Dosa; Salva Piscopo; Adekunle Hakeem Temitope; Sadaf Noor; Daniel-Ovidiu Costea (Critical Reviews in Food Science and Nutrition, 2023)

Investigating catalytic oxidative desulfurization of model fuel using hollow PW12/TiO2@MgCO3 and performance optimization via box-behnken design - Sadaf Ul Hassan; Hamna Khalid; Sidra Shafique; Muhammad Asim Farid; Muhammad Haris Saeed; Zulfiqar Ali; Muhammad Shahid Nazir; Murid Hussain; Young-Kwon Park (Chemosphere, 2023)

Groundwater level monitoring network design with machine learning methods - Sadaf Teimoori; Mohammad Hessam Olya; Carol J. Miller (Journal of Hydrology, 2023)

Application of nanoemulsion based edible coating on fresh-cut papaya - Nazia Tabassum; Rameez Ahmad Aftab; Owais Yousuf; Sadaf Ahmad; Sadaf Zaidi (Journal of Food Engineering, 2023)

Cellulose-based adsorbent materials for water remediation: Harnessing their potential in heavy metals and dyes removal - Awais Ali Aslam; Sadaf Ul Hassan; Muhammad Haris Saeed; Osama Kokab; Zulfiqar Ali; Muhammad Shahid Nazir; Waleed Siddiqi; Aamir Ali Aslam (Journal of Cleaner Production, 2023)

Impact Analysis of Internalizing Environmental Costs on Technical, Economic, and Environmental Performances for Power Plants - Sadaf Ziyaei; Mostafa Panahi; Davoud Manzour; Abdolreza Karbasi; Hamidreza Ghaffarzadeh (International Journal of Environmental Research, 2023)

New developments and future challenges in reducing and controlling heat island effect in urban areas - Alireza Karimi; Pir Mohammad; Antonio García-Martínez; David Moreno-Rangel; Darya Gachkar; Sadaf Gachkar (Environment, Development and Sustainability, 2023)

Scientific considerations in the regulatory approval of generic (or biosimilar) version of enoxaparin sodium – A lifesaving carbohydrate polymer - Zarina Iqbal; Saima Sadaf (Regulatory Toxicology and Pharmacology, 2023)

Piriformospora indica alter root-associated microbiome structure to enhance Artemisia annua L. tolerance to arsenic - Saeed ur Rahman; Muhammad Khalid; Nan Hui; Asad Rehman; Sadaf-Ilyas Kayani; Xueqing Fu; Han Zheng; Jin Shao; Abid Ali Khan; Mehran Ali; Ayat Taheri; Hang Liu; et al. (Journal of Hazardous Materials, 2023)

Bacteriological quality assessment of poultry chicken meat and meat contact surfaces for the presence of targeted bacteria and determination of antibiotic resistance of Salmonella spp. in Pakistan - Sadaf Tagar; Naveed Ahmed Qambrani (Food Control, 2023)

Valorizing waste palm oil towards biodiesel production using calcareous eggshell based heterogeneous catalyst - Wasi Ur Rahman; Rashid Imran Ahmad Khan; Sadaf Ahmad; Syed Mohd Yahya; Zahid A. Khan; Samuel Lalthazuala Rokhum; Gopinath Halder (Bioresource Technology Reports, 2023)

Seaweed-derived bio-stimulant improves growth and salt tolerance of radish varieties under saline conditions - Sadaf Gul; Zainul Abideen; Muhammad Yousuf Adnan; Maria Hanif; Muhammad Farrakh Nawaz; Shumaila; Ali El- Keblawy (Biocatalysis and Agricultural Biotechnology, 2023)

COVID-19: A novel holistic systems biology approach to predict its molecular mechanisms (in vitro) and repurpose drugs - Marzieh Sameni; Seyed Amir Mirmotalebisohi; Sadaf Dadashkhan; Sepideh Ghani; Maryam Abbasi; Effat Noori; Hakimeh Zali (DARU Journal of Pharmaceutical Sciences, 2023)

Nutritional and surgical aspects in prostate disorders - Amin Gasmi; Geir Bjørklund; Sadaf Noor; Yuliya Semenova; Alexandru Dosa; Joeri J. Pen; Alain Menzel; Salva Piscopo; Nicolas Wirth; Daniel-Ovidiu Costea (Critical Reviews in Food Science and Nutrition, 2023)

An insight into the hepatoprotective role of Velpatasvir and Sofosbuvir per se and in combination against carbon tetrachloride-induced hepatic fibrosis in rats - Sadaf Yasmeen; Aslam Khan; Fareeha Anwar; Muhammad Furqan Akhtar; Sidra Yasmeen; Shafeeq Ali Shah (Environmental Science and Pollution Research, 2023)

Recent Advances on the Pragmatic Roles of Phytomelatonin and Its Exogenous Application for Abiotic Stress Management in Plants - Sadaf Jan; Bhupender Singh; Renu Bhardwaj; Rattandeep Singh; Sheikh Mansoor; Parvaiz Ahmad (Journal of Plant Growth Regulation, 2023)

Exogenous Strigolactone (GR24) Positively Regulates Growth, Photosynthesis, and Improves Glandular Trichome Attributes for Enhanced Artemisinin Production in Artemisia annua - Kaiser Iqbal Wani; Andleeb Zehra; Sadaf Choudhary; M. Naeem; M. Masroor A. Khan; Riyazuddeen Khan; Tariq Aftab (Journal of Plant Growth Regulation, 2023)

Impact of green human resource management on green creativity in pharmaceutical companies: mediation role of green mindset - Muhammad Haseeb Shakil; Rana Nadir Idrees; Sadaf Ehsan; Waseem Anwar (Environmental Science and Pollution Research, 2023)

Enhancing biomass productivity towards carbohydrates and fatty acids biosynthesis under the effects of magneto-electric composite fields on filamentous algae - Sadaf-Ilyas Kayani; Nana Jin; Yi Cui; Xinyi Zan; Xinjuan Hu; Xiangru Xu; Feifei Zhu; Cunsheng Zhang; Shuhao Huo (Biomass and Bioenergy, 2023)

Geotechnical properties of problematic expansive subgrade stabilized with guar gum biopolymer - Muhammad Hamza; Zhihong Nie; Mubashir Aziz; Nauman Ijaz; Chuanfeng Fang; Muhammad Usman Ghani; Zain Ijaz; Sadaf Noshin; Muhammad Salman (Clean Technologies and Environmental Policy, 2023)

Industry 4.0 innovations and their implications: An evaluation from sustainable development perspective - Iqra Sadaf Khan; Muhammad Ovais Ahmad; Jukka Majava (Journal of Cleaner Production, 2023)

Commercial Low Molecular Weight Heparins — Patent Ecosystem and Technology Paradigm for Quality Characterization - Zarina Iqbal; Saima Sadaf (Journal of Pharmaceutical Innovation, 2023)

Interdisciplinary assessment of fisheries sustainability in Wular Lake, India - Regu Atufa; Pachampalayam Shanmugam Ananthan; Masood‐ul Hassan Balkhi; Sadaf Gul (Fisheries Management and Ecology, 2023)
Inland fisheries, including aquaculture, contributed 73.65% of India's total fish production of 14.16 million tons in 2019–2020. Wular Lake, one of the largest freshwater lakes in Asia with a 13,000 ha area and a notable Ramsar wetland of international importance, supports thriving but increasingly threatened endemic fisheries that supply almost one‐fourth of Jammu and Kashmir's fish catch and supports livelihoods of 3147 families of indigenous communities in a remote Himalayan region of India. A modified multi‐dimensional RAPFISH methodology was used to ascertain the sustainability of the lake's fisheries. Catch records and published literature formed secondary data sources while primary information was collected through detailed key informant interviews, focus group discussions and participant observation methods, among both resource users and resource managers during 2018–2019. With a RAPFISH score of 40%, Wular lake fisheries fell in a less sustainable category, which is a cause of concern. Along with the technology evaluation field, which fared worst with a poor score of 15.77%, social (30.39%) and governance (39.09%) fields were less sustainable, while economic (69.33%) and ecology fields (57.68%) fell in the quite sustainable category. Very poor education level, high population density, minimal infrastructure, primitive craft, increasing pollution and ineffective governance are prime drivers of low sustainability. Variability in scores of evaluation fields and indicators supports the validity and utility of the modified RAPFISH tool for illuminating multi‐dimensionality and complexity of lake fishery management. In the context of sustaining a small‐scale artisanal fishery and associated livelihoods, our findings suggest specific evidence‐based interventions to improve the sustainability of lake fisheries that can avoid tragedy of commons problem.

Halotolerant bacterial biofilms for desalination and water treatment: a pilot study - Sadaf Jahan Gauhar; Aisha Waheed Qurashi; Iram Liaqat; Urooj Zafar; Muhammad Arshad Virk; Chaman Ara; Mehwish Faheem; Muhammad Mubin (Environmental Science and Pollution Research, 2023)

Comment on “Genotoxicity of organic contaminants in the soil: A review based on bibliometric analysis and methodological progress” - Sadaf Khan; Saddam Hussain; Waseem Hassan (Chemosphere, 2023)

The prevalence of pharmacogenetic variants of vitamin K epoxide reductase complex subunit 1 gene (rs9923231), cytochrome P450 family 2 subfamily C member 9 gene (rs1799853) and cytochrome P450 family 3 subfamily-A member-5 gene (rs776746) among 13 ethnic groups of Pakistan - Sadaf Firasat; Ali Raza; Abdul Rafay Khan; Aiysha Abid (Molecular Biology Reports, 2023)

Delayed Differentiation in Fertilizer Production: Deciphering Climate-Smart Miscible Products through Reverse Blending for Boosting Crop Production - Tahir Sheikh; Zahoor Baba; Zahoor A. Ganie; Basharat Hamid; Ali Mohd Yatoo; Ansar ul Haq; Sadaf Iqbal; Fehim J. Wani; Sivagamy Kannan; Roheela Ahmad (Journal of Soil Science and Plant Nutrition, 2023)

Impacts of Smoking and Stomach Disorders on Essential Elements in Biological Samples of Cement and Glass Industrial Workers - Sadaf Parveen; Hassan Imran Afridi; Tasneem Gul Kazi; Farah Naz Talpur; Jameel Ahmed Baig; Ghulam Qadir Chanihoon; Ahsan Ali Memon; Almas Rahoojo (Biological Trace Element Research, 2023)

Photocatalytic degradation of industrial dye using hybrid filler impregnated poly-sulfone membrane and optimizing the catalytic performance using Box-Behnken design - Sadaf Ul Hassan; Sidra Shafique; Bushra Anees Palvasha; Muhammad Haris Saeed; Syed Ali Raza Naqvi; Sohail Nadeem; Syed Irfan; Toheed Akhter; Asim Laeeq Khan; Muhammad Shahid Nazir; Murid Hussain; Young-Kwon Park (Chemosphere, 2023)

A novel framework-based meta-analysis for in-depth characterization of microplastic pollution and associated ecological risks in Chinese Bays - Shulin Liu; Muhammad Junaid; Mamona Sadaf; Wenjie Ai; Xue Lan; Jun Wang (Journal of Hazardous Materials, 2023)

Potential candidates from marine and terrestrial resources targeting mitochondrial inhibition: Insights from the molecular approach - Saikat Mitra; Abdur Rauf; Hriday Sutradhar; Samia Sadaf; Md. Jamal Hossain; Mahfuza Afroz Soma; Talha Bin Emran; Bashir Ahmad; Abdullah S.M. Aljohani; Waleed Al Abdulmonem; Muthu Thiruvengadam (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Determination of seroprevalence of brucellosis in livestock and high-risk population in Kurdistan, Western Iran - Shadi Aghamohammad; Mojtaba Rastin; Ehsan Mostafavi; Arian Hajijafari Anaraki; Maryam Rahravani; Reza Atashin Sadaf; Meysam Moravedji; Mahdi Rohani (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Effects of age, body weight, semen collection frequency and holding duration on semen traits of broiler breeder reared under different housing systems - Muhammad Shabir Shaheen; Sadaf Aslam; Shahid Mehmood; Muhammad Tariq; Yassar Abbas; Hassan Ashfaq; Sohail Ahmad (Tropical Animal Health and Production, 2023)

Cellular Responses, Osmotic Adjustments, and Role of Osmolytes in Providing Salt Stress Resilience in Higher Plants: Polyamines and Nitric Oxide Crosstalk - Sadaf Choudhary; Kaiser Iqbal Wani; M. Naeem; M. Masroor A. Khan; Tariq Aftab (Journal of Plant Growth Regulation, 2023)

Nutritional value, phytochemicals and antioxidant status of Artemia urmiana enriched with premix extract of brown macroalgae Padina australis, Sargassum ilicifolium, and Stoechospermum marginatum - Paria Akbary; Ashkan Ajdari; Salim Jadgal; Danial Ajdari; Raha Fadaii Raeini; Seyed Ahmad Reza Hashemi; Elnazs Erfanifar; Mohamad Saeid Fereidouni; Sadaf Meikolaei (Journal of Applied Phycology, 2023)

Role of morphology and chemical composition of PM for particle deposition in human respiratory system: A case study over megacity-Delhi - Sadaf Fatima; Sumit Kumar Mishra; Uma Kumar; Ajit Ahlawat; Tulsi Satyavir Dabodiya; Dheeraj Khosla (Urban Climate, 2023)

Perinatal exposure to environmental endocrine disruptor bisphenol A aggravates the onset of non-alcoholic fatty liver disease (NAFLD) in weanling F1 offspring of obese rats - Sadaf Dabeer; Sheikh Raisuddin (Environmental Science and Pollution Research, 2023)

Sustainable power generation through decarbonization in the power generation industry - Sadaf Ziyaei; Mostafa Panahi; Davoud Manzour; Abdolreza Karbasi; Hamidreza Ghaffarzadeh (Environmental Monitoring and Assessment, 2023)

Effect of Berberine and Blue LED Irradiation on Combating Biofilm of Pseudomonas aeruginosa and Staphylococcus aureus - Sadaf Mahuti Safai; Khatereh Khorsandi; Sarvenaz Falsafi (Current Microbiology, 2022)

EMS-based mutants are useful for enhancing drought tolerance in spring wheat - Sadaf Zahra; Momina Hussain; Sana Zulfiqar; Shumila Ishfaq; Tayyaba Shaheen; Muhammad Akhtar; Mehboob-ur-Rahman (Cereal Research Communications, 2022)

Evaluation of unconventional hydrocarbon reserves using petrophysical analysis to characterize the Yageliemu Formation in the Yakela gas condensate field, Tarim Basin, China - Wakeel Hussain; Lin Pan; Xiao Wang; Muhammad Saqlain; Muhammad Ali; Rakhshanda Sadaf; Nafees Ali; Irshad Hussain; Sajid Ali; Mazahir Hussain; Ali Asghar (Arabian Journal of Geosciences, 2022)

Evaluation of water supply system performance affected by climate change with MODSIM modeling and reservoir efficiency indicators - Sadaf-Sadat Mortezaeipooya; Parisa-Sadat Ashofteh; Parvin Golfam; Hugo A. Loáiciga (Arabian Journal of Geosciences, 2022)

Modeling the upshots of induced temperature and water stress on germination and seedlings length of radish (Raphanus sativus L.) via hydrothermal time model - Jalal Khan; Sami Ullah; Sikandar Shah; Sadaf; Sheharyar Khan; Sulaiman (Vegetos, 2022)
Radish ( Raphanus sativus L.), a representative of the Brassicaceae family, is an extensively cultivated root vegetable across the world. Thermal time (TT), hydro time (HT), and hydrothermal time (HTT) models can be used to characterize the response of seed germination rate to temperature (T) and water potential ( ψ ). The germination behavior of radish was investigated throughout a range of constant temperatures and water potentials to evaluate the effectiveness of hydro-thermal time model and offer a data set of germination thresholds and parameters. The study was intended to simultaneously inspect the radish seed germination (SG) pattern, base water potentials ( ψ b(50) ) and cardinal temperatures across varying temperatures ( T s ) and PEG-6000 water potentials ( Ψ s ) via the hydrothermal time (HTT) model. In a laboratory experiment Raphanus sativus L. seeds were germinated at four constant T s of 15, 20, 30 and 40 °C under four different water potentials ( ψs) of 0, − 0.2, − 0.4 and − 0.6 MPa. Germination decreased significantly at ( p ≤ 0.01) from 40% at 15 °C in − 0.2 MPa to 13% in − 0.8 MPa at 40 °C. The results also revealed that radish was more sensitive to ψ than T (p ≤ 0.01). As per the significance level of the model attributes ( R 2 : 0.527), the average cardinal temperatures were 15, 20 and 40 °C for the base ( T b ), optimal ( T o ) and ceiling ( T c ) temperatures respectively. Germination energy (GE), germination rate index (GRI), germination percentage (G%), germination index (GI), mean moisture content (MMC), seed vigor index 1 and 2 (SVI-1 and SVI-2), were recorded maximum in control condition at 15 and 20 °C and minimum at − 0.8 MPa at 40 °C. The model applied here, and its attributes, may be used as a prediction tool in different SG simulation studies, each with its own set of strengths and drawbacks. The hydrothermal constant investigates the interaction influence of T and ψ on germination under diverse ecological settings using germination data, cardinal temperatures, and statistical analysis.

Structural and Electronic (Absorption and Fluorescence) Properties of a Stable Triplet Diphenylcarbene: A DFT Study - Abrar Ul Hassan; Ayesha Mohyuddin; Sohail Nadeem; Cihat Güleryüz; Sadaf Ul Hassan; Mohsin Javed; Muhammad Salman Muhsan (Journal of Fluorescence, 2022)

miR-106b enhances human mesenchymal stem cell differentiation to spermatogonial stem cells under germ cell profile genes involved in TGF-b signaling pathways - Sadaf Mahboudi; Kazem Parivar; Zohreh Mazaheri; Shiva Irani (In Vitro Cellular & Developmental Biology - Animal, 2022)

Selecting the Best Approach to Modeling the Performance of Water Supply System Using the Combination of Rough Set Theory with Multi-Criteria Decision Making - Sadaf-Sadat Mortezaeipooya; Parisa-Sadat Ashofteh; Parvin Golfam (Water Resources Management, 2022)

COVID-19 outbreak and air quality of Lahore, Pakistan: evidence from asymmetric causality analysis - Aisha Tauqir; Sadaf Kashif (Modeling Earth Systems and Environment, 2022)

Correlating the charge transfer efficiency of metallic sulfa-isatins to design efficient NLO materials with better drug designs - Sadaf Noreen; Sajjad H. Sumrra (BioMetals, 2022)

New insights into Perrault syndrome, a clinically and genetically heterogeneous disorder - Rabia Faridi; Alessandro Rea; Cristina Fenollar-Ferrer; Raymond T. O’Keefe; Shoujun Gu; Zunaira Munir; Asma Ali Khan; Sheikh Riazuddin; Michael Hoa; Sadaf Naz; William G. Newman; Thomas B. Friedman (Human Genetics, 2022)

Molecular genetic landscape of hereditary hearing loss in Pakistan - Sadaf Naz (Human Genetics, 2022)

Doxorubicin-Induced Cardiotoxicity: An Overview on Pre-clinical Therapeutic Approaches - Mohammad Sheibani; Yaser Azizi; Maryam Shayan; Sadaf Nezamoleslami; Faezeh Eslami; Mohammad Hadi Farjoo; Ahmad Reza Dehpour (Cardiovascular Toxicology, 2022)

Genetic Association of Butyrylcholinesterase with Major Depressive Disorder - Sliha Awan; Aisha N. Hashmi; Rizwan Taj; Sadaf Munir; Rabia Habib; Sajida Batool; Maleeha Azam; Raheel Qamar; Syed M. Nurulain (Biochemical Genetics, 2022)

Strauss point modeling for seismic activity: a case study of earthquakes - Amna Zahra; Ijaz Hussain; Muhammad Zaffar Hashmi; Muhammad Faisal; Elsayed Elsherbini Elashkar; Sadaf Shamshoddin Soudagar; Fares Fawzi Al-Deek; Mohammed Ageli (Modeling Earth Systems and Environment, 2022)

Formulation of Apigenin-Cyclodextrin-Chitosan Ternary Complex: Physicochemical Characterization, In Vitro and In Vivo Studies - Mohammed Jafar; Mohammed Saifuddin Khalid; Hajer Alghamdi; Mohd Amir; Sarah Aon Al Makki; Ohud Saud Alotaibi; Afnan Ali Al Rmais; Syed Sarim Imam; Sultan Alshehri; Sadaf Jamal Gilani (AAPS PharmSciTech, 2022)

Bio-diesel production of sunflower through sulphur management in a semi-arid subtropical environment - Athar Mahmood; Masood Iqbal Awan; Sana Sadaf; Ahmed Mukhtar; Xiukang Wang; Sajid Fiaz; Sher Aslam Khan; Habib Ali; Faran Muhammad; Zafar Hayat; Farhana Gul; Shah Fahad (Environmental Science and Pollution Research, 2022)

Bacterial prediction using internet of things (IoT) and machine learning - Hamza Khurshid; Rafia Mumtaz; Noor Alvi; Ayesha Haque; Sadaf Mumtaz; Faisal Shafait; Sheraz Ahmed; Muhammad Imran Malik; Andreas Dengel (Environmental Monitoring and Assessment, 2022)

The relevance of economic freedom for energy, environment, and economic growth in Asia-Pacific region - Muhammad Tariq Mahmood; Sadaf Shahab; Muhammad Shahbaz (Environmental Science and Pollution Research, 2022)

The Role of Diet and Supplementation of Natural Products in COVID-19 Prevention - Amin Gasmi; Salvatore Chirumbolo; Massimiliano Peana; Sadaf Noor; Alain Menzel; Maryam Dadar; Geir Bjørklund (Biological Trace Element Research, 2022)

Enhanced biomass production of Synechocystis sp. PCC 6803 by two associated bacteria Paenibacillus camelliae and Curtobacterium ammoniigenes - Sadaf Tanweer; Karisma Dash; Bhabatarini Panda (Archives of Microbiology, 2022)

Impact of water–sediment interaction on hydrogeochemical signature of dug well aquifer by using geospatial and multivariate statistical techniques of Islamkot sub-district, Tharparkar district, Sindh, Pakistan - Muhammad Soomar Samtio; Khadim Hussain Rajper; Asghar Ali alias Daahar Hakro; Muhammad Farooque Lanjwani; Abdul Qayoom Mughari; Rakhshanda Sadaf; Riaz Hussain Rajper; Abdul Shakoor Mastoi; Muhammad Hassan Agheem; Rafique Ahmed Lashari; Taj Muhmmad Jahangir (Arabian Journal of Geosciences, 2022)

Nitric Oxide: A Ubiquitous Signal Molecule for Enhancing Plant Tolerance to Salinity Stress and Their Molecular Mechanisms - Savita Bhardwaj; Dhriti Kapoor; Simranjeet Singh; Vandana Gautam; Daljeet Singh Dhanjal; Sadaf Jan; Praveen C. Ramamurthy; Ram Prasad; Joginder Singh (Journal of Plant Growth Regulation, 2021)

RETRACTED ARTICLE: Measuring technical efficiency associated with environmental investment: does market competition and risk matters in banking sector - Supat Chupradit; Dai Yannan; Hafiz Waqas Kamran; Sadaf S. Soudagar; Alaa Mohamd Shoukry; Jameel A. Khader (Environmental Science and Pollution Research, 2021)

Buffalo Infection by Fasciola gigantica Transmitted by Radix acuminata in Uttar Pradesh, India: A Molecular Tool to Improve Snail Vector Epidemiology Assessments and Control Surveillance - Kumari Sunita; Santiago Mas-Coma; Maria Dolores Bargues; Sadaf; Mohammad Aasif Khan; Maria Habib; Saad Mustafa; Syed Akhtar Husain (Acta Parasitologica, 2021)

Comprehensive Mutation Analysis and Report of 12 Novel Mutations in a Cohort of Patients with Spinal Muscular Atrophy in Iran - Zohreh Sharifi; Mohammad Taheri; Mohammad-Sadegh Fallah; Maryam Abiri; Fatemeh Golnabi; Hamideh Bagherian; Razieh Zeinali; Hossein Farahzadi; Marjan Alborji; Pardis Ghazizadeh Tehrani; Masoume Amini; Sadaf Asnavandi; et al. (Journal of Molecular Neuroscience, 2021)

Metformin in the management of fibrocystic breast disease: a placebo-controlled randomized clinical trial - Sadaf Alipour; Hadith Rastad; Azin Saberi; Firoozeh Faiz; Arezoo Maleki-Hajiagha; Mahboubeh Abedi (DARU Journal of Pharmaceutical Sciences, 2021)

Mechanistic Insights into Strigolactone Biosynthesis, Signaling, and Regulation During Plant Growth and Development - Kaiser Iqbal Wani; Andleeb Zehra; Sadaf Choudhary; M. Naeem; M. Masroor A. Khan; Christian Danve M. Castroverde; Tariq Aftab (Journal of Plant Growth Regulation, 2021)

Production and characterization of Komagataeibacter xylinus SGP8 nanocellulose and its calcite based composite for removal of Cd ions - Amrik Bhattacharya; Ayesha Sadaf; Swati Dubey; Rajesh P. Singh; Sunil Kumar Khare (Environmental Science and Pollution Research, 2021)

Enhancing artemisinin content in and delivery from Artemisia annua: a review of alternative, classical, and transgenic approaches - Kaiser Iqbal Wani; Sadaf Choudhary; Andleeb Zehra; M. Naeem; Pamela Weathers; Tariq Aftab (Planta, 2021)

Promoting Colorectal Cancer Screening in South Asian Muslims Living in the USA - Eiman Kazi; Sadaf Sareshwala; Zahra Ansari; Dilpreet Sahota; Toshali Katyal; Winston Tseng; Susan L. Ivey (Journal of Cancer Education, 2021)

Sunlight-induced photocatalytic degradation of various dyes and bacterial inactivation using CuO–MgO–ZnO nanocomposite - Tauseef Munawar; Faisal Mukhtar; Sadaf Yasmeen; Muhammad Naveed-ur-Rehman; Muhammad Shahid Nadeem; Muhammad Riaz; Muhammad Mansoor; Faisal Iqbal (Environmental Science and Pollution Research, 2021)

Neurological Manifestation of SARS-CoV-2 Induced Inflammation and Possible Therapeutic Strategies Against COVID-19 - Dipak Kumar; Sadaf Jahan; Andleeb Khan; Arif Jamal Siddiqui; Neeru Singh Redhu; Wahajuddin; Johra Khan; Saeed Banwas; Bader Alshehri; Mohammed Alaidarous (Molecular Neurobiology, 2021)

Bismuth vanadate/MXene (BiVO4/Ti3C2) heterojunction composite: enhanced interfacial control charge transfer for highly efficient visible light photocatalytic activity - Muhammad Munir Sajid; Sadaf Bashir Khan; Yasir Javed; Nasir Amin; Zhengjun Zhang; Naveed Akhtar Shad; Haifa Zhai (Environmental Science and Pollution Research, 2021)

Support vector regression-based model for phenol adsorption in rotating packed bed adsorber - Rameez Ahmad Aftab; Sadaf Zaidi; Mohd Danish; Sayed Mohammad Adnan; Khursheed B. Ansari; Mohammad Danish (Environmental Science and Pollution Research, 2021)

Temporal and seasonal variations of noise pollution in urban zones: a case study in Pakistan - Sadaf Munir; Sardar Khan; Shahla Nazneen; Sheikh Saeed Ahmad (Environmental Science and Pollution Research, 2021)

Detection and disinfection of COVID-19 virus in wastewater - Simranjeet Singh; Vijay Kumar; Dhriti Kapoor; Daljeet Singh Dhanjal; Deepika Bhatia; Sadaf Jan; Nasib Singh; Romina Romero; Praveen C. Ramamurthy; Joginder Singh (Environmental Chemistry Letters, 2021)

Dietary quality using four dietary indices and lung cancer risk: the Golestan Cohort Study (GCS) - Qian Wang; Maryam Hashemian; Sadaf G. Sepanlou; Maryam Sharafkhah; Hossein Poustchi; Masoud Khoshnia; Abdolsamad Gharavi; Akram Pourshams; Akbar Fazeltabar Malekshah; Farin Kamangar; Arash Etemadi; Christian C. Abnet; et al. (Cancer Causes & Control, 2021)

High effective removal of diazinon from aqueous solutions using the magnetic tragacanth-montmorillonite nanocomposite: isotherm, kinetic, and mechanism study - Sadaf Nikzad; Ali Akbar Amooey; Ali Alinejad-Mir (Environmental Science and Pollution Research, 2021)

gPROMS-driven modeling and simulation of fixed bed adsorption of heavy metals on a biosorbent: benchmarking and case study - Mohd Danish; Khursheed B. Ansari; Rameez Ahmad Aftab; Mohammad Danish; Sadaf Zaidi; Quang Thang Trinh (Environmental Science and Pollution Research, 2021)

Wet spells over the core monsoon domain of northern Pakistan during the summer season - Nabeela Sadaf; Yanluan Lin; Wenhao Dong (International Journal of Climatology, 2021)
Flooding events or wet spells have increased over Pakistan in recent years. However, a long‐term classification of large‐scale and synoptic‐scale configuration for these events has been lacking. In this study, a total of 53 wet spells during the period of 1951–2015 over the core monsoon domain of northern Pakistan are identified using rainfall data. Based on daily geopotential height fields from NCEP/NCAR re‐analysis, the dominant synoptic‐scale systems, displaying distinct low‐level circulation and moisture transport, are found during these wet spells over Pakistan. They are categorized as trough with low pressure system (LPS, 30 cases), trough without LPS (19 cases) and LPS only (4 cases) wet spells. Without the accompanying LPS over India, the trough tends to be deep and intrudes to southern Pakistan with moisture transport mainly from the Arabian Sea. In contrast, the trough is relatively shallow and interacts with presence of the LPS to steer moisture from the Bay of Bengal towards Pakistan. We found that subtropical trough is an essential ingredient of wet spells over Pakistan. This is different from wet spells over the core monsoon domain of India, which is mainly dominated by LPS. The ridge development over Siberia is a precursor to wet spells over Pakistan and provides guidance for prediction.

Specialist recommendation for chemoprevention medications in patients at familial risk of breast cancer: a cross-sectional survey in England - Siang Ing Lee; Helen Curtis; Sadaf Qureshi; Brittany Dutton; Nadeem Qureshi (Journal of Community Genetics, 2021)
In England, the National Institute for Health and Care Excellence guideline for familial breast cancer recommends chemoprevention for women at high and moderate familial risk of breast cancer. However, prescribing of chemoprevention has not improved since the introduction of the guideline in 2013. The study aims to identify the current practice, in England, of familial cancer specialists offering chemoprevention and recommending prescribing in primary care. This was an anonymized national cross-sectional survey of familial breast cancer risk services in England. Lead clinicians were sent an online survey link. The survey questions included whether chemoprevention was offered/considered for high- and moderate-risk women, when chemoprevention prescribing and recommendation to primary care started, medications prescribed, age groups considered for chemoprevention, and existence of a shared prescribing protocol with primary care. The survey was sent to 115 hospital services; responses from 50 services (43%) were included in the analysis. Of the 40 services offering chemoprevention for high-risk women, 15 (38%) did not prescribe but 31 (78%) recommended prescribing to primary care. Of the 31 services considering chemoprevention for moderate risk, eight (26%) did not prescribe with 26 (84%) recommended prescribing to primary care. Only three services reported having a shared protocol with primary care. Within 3 years of the guidelines, many services recognized the role of chemoprevention for both high and moderate risk with a key role for primary care to initiate prescribing. However, there is still room for improvement.

Monitoring responses of vegetation phenology and productivity to extreme climatic conditions using remote sensing across different sub-regions of China - Tehseen Javed; Yi Li; Kai Feng; Olusola O. Ayantobo; Shakeel Ahmad; Xinguo Chen; Sadaf Rashid; Sovannaka Suon (Environmental Science and Pollution Research, 2021)

Systematic study of the new remains of Propotamochoerus hysudricus (Suidae, Mammalia) from the Late Miocene–Early Pliocene of Middle Siwaliks (Pakistan) - Sadaf Aslam; Abdul Majid Khan; Rana Manzoor Ahmad; Ayesha Iqbal; Muhammad Tahir Waseem (Arabian Journal of Geosciences, 2021)

The Relevance of SNPs at 3′UTR Region of CASP7 and miR-371b-5p Associated Diseases: A Computational Analysis - Muhammad Safdar; Sana Zaheer; Rozhgar A. Khailany; Sadaf Parvez; Muhammad Naveed; Piplu Bhuiyan; Mehmet Ozaslan; Rebaz Moatasam; Mustafa S. Al-Attar; Musarrat Abbas Khan; Yasmeen Junejo (Cell Biochemistry and Biophysics, 2020)

The potential of Allium sativum and Cannabis sativa extracts for anti-tick activities against Rhipicephalus (Boophilus) microplus - Nasreen Nasreen; Sadaf Niaz; Adil Khan; Muhammad Arfan Zaman; Sultan Ayaz; Huma Naeem; Nasrullah Khan; Abdallah M. Elgorban (Experimental and Applied Acarology, 2020)

Induction of growth and antioxidant defense mechanisms in Matricaria chamomilla L. callus by vibration - Sadaf Salami; Halimeh Hassanpour; Vahid Niknam (In Vitro Cellular & Developmental Biology - Plant, 2020)

Lithium reverses the effect of opioids on eNOS/nitric oxide pathway in human umbilical vein endothelial cells - Sadaf Nezamoleslami; Mohammad Sheibani; Faiza Mumtaz; Jamileh Esmaeili; Hamed Shafaroodi; Ahmad Reza Dehpour (Molecular Biology Reports, 2020)

Optimization of process parameters for the synthesis of silver nanoparticles from Piper betle leaf aqueous extract, and evaluation of their antiphytofungal activity - Sadaf Khan; Simran Singh; Swapnil Gaikwad; Neelu Nawani; Manisha Junnarkar; Sarika Vishnu Pawar (Environmental Science and Pollution Research, 2020)

Synthesis of cost-effective magnetic nano-biocomposites mimicking peroxidase activity for remediation of dyes - Ayesha Sadaf; Razi Ahmad; Achraf Ghorbal; Walid Elfalleh; Sunil Kumar Khare (Environmental Science and Pollution Research, 2020)

Influence of Crapemyrtle aphid, Tinocallis kahawaluokalani (Hemiptera: Aphididae) on population characteristics of three aphidophagous ladybird beetles - Muhammad Asif Aziz; Habiba Sadaf; Ayesha Iftikhar; Faisal Hafeez (International Journal of Tropical Insect Science, 2020)

Impact of Long-Term Copper Exposure on Growth, Photosynthesis, Antioxidant Defence System and Artemisinin Biosynthesis in Soil-Grown Artemisia annua Genotypes - Andleeb Zehra; Sadaf Choudhary; Mohammad Mukarram; M. Naeem; M. Masroor A. Khan; Tariq Aftab (Bulletin of Environmental Contamination and Toxicology, 2020)

The emergence of an unassigned complex recombinant form in a Pakistani HIV-infected individual - Uroosa Tariq; Ayesha Iftikhar; Dilsha Zahid; Faisal Sultan; Syed Faisal Mahmood; Sadaf Naeem; Syed Ali; Syed Hani Abidi (Archives of Virology, 2020)

Energy capacity, industrial production, and the environment: an empirical analysis from Pakistan - Muhammad Tariq Mahmood; Sadaf Shahab; Muhammad Hafeez (Environmental Science and Pollution Research, 2020)

Biological Activities of Artemisinins Beyond Anti-Malarial: a Review - Saeed-ur-Rahman; Muhammad Khalid; Sadaf-Ilyas Kayani; Farooq Jan; Ayaz Ullah; Kexuan Tang (Tropical Plant Biology, 2019)

Harnessing natural colorants from algal species for fabric dyeing: a sustainable eco-friendly approach for textile processing - Muhammad Azeem; Naeem Iqbal; Riffat Ayesha Mir; Shahid Adeel; Fatima Batool; Ali Ahmad Khan; Sadaf Gul (Journal of Applied Phycology, 2019)

Detection of Emotions Induced by Colors in Compare of Two Nonlinear Mapping of Heart Rate Variability Signal: Triangle and Parabolic Phase Space (TPSM, PPSM) - Sadaf Moharreri; Nader Jafarnia Dabanloo; Keivan Maghooli (Journal of Medical and Biological Engineering, 2019)

Correction to: Differentiating neurons derived fromhuman umbilical cord blood stem cells work as a test system for developmental neurotoxicity - Mahendra P. Kashyap; Vivek Kumar; Abhishek K. Singh; Vinay K. Tripathi; Sadaf Jahan; Ankita Pandey; Ritesh K. Srivastava; Vinay K. Khanna; Aditya B. Pant (Molecular Neurobiology, 2019)

Neuroprotective effect of diclofenac on chlorpromazine induced catalepsy in rats - Sadaf Naeem; Rahila Najam; Saira Saeed Khan; Talat Mirza; Bushra Sikandar (Metabolic Brain Disease, 2019)

Neuro-pharmacological evaluation of anticonvulsant and neuroprotective activity of Cocculus laurifolius leaves in wistar rats - Sidra Maqbool; Ishrat Younus; Rafia Sadaf; Anab Fatima (Metabolic Brain Disease, 2019)

Green algae, Cladophora glomerata L.–based natural colorants: dyeing optimization and mordanting for textile processing - Riffat Ayesha Mir; Shahid Adeel; Muhammad Azeem; Fatima Batool; Ali Ahmad Khan; Sadaf Gul; Naeem Iqbal (Journal of Applied Phycology, 2019)

Acaricidal efficacy of Calotropis procera (Asclepiadaceae) and Taraxacum officinale (Asteraceae) against Rhipicephalus microplus from Mardan, Pakistan - Adil Khan; Nasreen Nasreen; Sadaf Niaz; Sultan Ayaz; Huma Naeem; Ijaz Muhammad; Fazal Said; Robert D. Mitchell; Adalberto A. Pérez de León; Snehil Gupta; Sachin Kumar (Experimental and Applied Acarology, 2019)

Identification of valid reference genes for the normalization of RT-qPCR gene expression data in Alexandrium catenella under different nutritional conditions - Zeeshan Niaz; Zhenghong Sui; Sadaf Riaz; Yuan Liu; Erlei Shang; Qikun Xing; Sohrab Khan; Qingwei Du; Wei Zhou; JinguoWang (Journal of Applied Phycology, 2019)

Spatial and temporal dynamics of dissolved nutrients and factors affecting water quality of Chilika lagoon - Sadaf Nazneen; N. Janardhana Raju; Sughosh Madhav; Arif Ahamad (Arabian Journal of Geosciences, 2019)

Biochemical Analysis and Association of Butyrylcholinesterase SNPs rs3495 and rs1803274 with Substance Abuse Disorder - Sadaf Munir; Rabia Habib; Sliha Awan; Nazia Bibi; Arooj Tanveer; Sajida Batool; Syed M. Nurulain (Journal of Molecular Neuroscience, 2019)

Estimating active storage of groundwater quality zones in alluvial deposits of Faisalabad area, Rechna Doab, Pakistan - Perveiz Khalid; Muhammad Sanaullah; Muhammed Javaid Sardar; Sadaf Iman (Arabian Journal of Geosciences, 2019)

Birth and death of Mx genes and the presence/absence of genes regulating Mx transcription are correlated with the diversity of anti-pathogenicity in vertebrate species - Furong Qi; Airong Yang; Sadaf Ambreen; Xue Bai; Yali Hou; Xuemei Lu (Molecular Genetics and Genomics, 2019)

Ecophysiological response of early stage Albizia lebbeck to cadmium toxicity and biochar addition - Muhammad Talha Bin Yousaf; Muhammad Farrakh Nawaz; Hammad Fayyaz Khawaja; Sadaf Gul; Shafaqat Ali; Irfan Ahmad; Fahd Rasul; Muhammad Rizwan (Arabian Journal of Geosciences, 2019)

CRISPR-Cas System: History and Prospects as a Genome Editing Tool in Microorganisms - Muhammad R. Javed; Maria Sadaf; Temoor Ahmed; Amna Jamil; Marium Nawaz; Hira Abbas; Anam Ijaz (Current Microbiology, 2018)

Microtubules are reorganised and fragmented for uterine receptivity - Sadaf N. Kalam; Samson Dowland; Laura Lindsay; Christopher R. Murphy (Cell and Tissue Research, 2018)

Hexadecylated linear PEI self-assembled nanostructures as efficient vectors for neuronal gene delivery - Ruby Bansal; Brashket Seth; Shashikant Tiwari; Sadaf Jahan; Manisha Kumari; Aditya Bhushan Pant; Rajnish Kumar Chaturvedi; Pradeep Kumar; Kailash Chand Gupta (Drug Delivery and Translational Research, 2018)

Nanotherapeutic approaches targeting angiogenesis and immune dysfunction in tumor microenvironment - Sadaf Hameed; Pravin Bhattarai; Zhifei Dai (Science China Life Sciences, 2018)

TOX3 Variants Are Involved in Restless Legs Syndrome and Parkinson’s Disease with Opposite Effects - Sadaf Mohtashami; Qin He; Jennifer A. Ruskey; Sirui Zhou; Patrick A. Dion; Richard P. Allen; Christopher J. Earley; Edward A. Fon; Lan Xiong; Nicolas Dupre; Yves Dauvilliers; Guy A. Rouleau; et al. (Journal of Molecular Neuroscience, 2018)

A Novel Multi-Scalar Drought Index for Monitoring Drought: the Standardized Precipitation Temperature Index - Zuliqar Ali; Ijaz Hussain; Muhammad Faisal; Hafiza Mamona Nazir; Mitwali Abd-el Moemen; Tajammal Hussain; Sadaf Shamsuddin (Water Resources Management, 2017)

Analytical study of the causes of the major landslide of Bukit Antarabangsa in 2008 using fault tree analysis - Danish Kazmi; Sadaf Qasim; I. S. H. Harahap; Thu Hang Vu (Innovative Infrastructure Solutions, 2017)

Landslide of Highland Towers 1993: a case study of Malaysia - Danish Kazmi; Sadaf Qasim; I. S. H. Harahap; Syed Baharom (Innovative Infrastructure Solutions, 2017)

A Probabilistic Study for the Analysis of the Risks of Slope Failure by Applying HEART Technique - Danish Kazmi; Sadaf Qasim; I. S. H. Harahap; Syed Baharom (Geotechnical and Geological Engineering, 2017)

Vanadium(V) complexes with hydrazides and their spectroscopic and biological properties - Sadaf Sultan; Uzma Ashiq; Rifat Ara Jamal; Mohammad Mahroof-Tahir; Zara Shaikh; Bushra Shamshad; Mehreen Lateef; Lubna Iqbal (BioMetals, 2017)

Ethnoveterinary health management practices using medicinal plants in South Asia – a review - Shanoo Suroowan; Faisal Javeed; Mushtaq Ahmad; Muhammad Zafar; Mehwish Jamil Noor; Sadaf Kayani; Ali Javed; Mohamad Fawzi Mahomoodally (Veterinary Research Communications, 2017)

Novel substituted 3-phenyl 1-(4-(5-bromopyridin-3-yl)-6-phenylpyrimidin-2-yl)-thiourea compounds as key small organic molecules for the potential treatment of type II diabetes mellitus: in vitro studies against yeast α-glucosidase - Tanzeel Ur Rehman; Islam Ullah Khan; Sadaf Riaz (Medicinal Chemistry Research, 2017)

The association of urinary interferon-gamma inducible protein-10 (IP10/CXCL10) levels with kidney allograft rejection - Ali Raza; Sadaf Firasat; Shagufta Khaliq; Tahir Aziz; Muhammed Mubarak; Syed Ali Anwar Naqvi; Syed Qasim Mehdi; Syed Adib-ul-Hasan Rizvi; Aiysha Abid (Inflammation Research, 2017)

Energy-water-food nexus under financial constraint environment: good, the bad, and the ugly sustainability reforms in sub-Saharan African countries - Khalid Zaman; Sadaf Shamsuddin; Mehboob Ahmad (Environmental Science and Pollution Research, 2017)

Spatial assessment of water quality parameters in Jhelum city (Pakistan) - Sadaf Javed; Asad Ali; Saleem Ullah (Environmental Monitoring and Assessment, 2017)

Distribution and sources of carbon, nitrogen, phosphorus and biogenic silica in the sediments of Chilika lagoon - Sadaf Nazneen; N Janardhana Raju (Journal of Earth System Science, 2017)

Chromium Exposure in the Adult Population, Consuming Different Types of Smokeless Tobacco Products in Pakistan - Asma Akhtar; Hasan Imran Afridi; Tasneem Gul Kazi; Farah Naz Talpur; Sadaf Sadia Arain; Jameel Ahmed Baig; Noman Khan; Mustafa Khan; Muhammad Bilal (Biological Trace Element Research, 2017)

Early detection of the effects of compaction in forested soils: evidence from selective extraction techniques - Muhammad Farrakh Nawaz; Guilhem Bourrié; Fabienne Trolard; Jacques Ranger; Sadaf Gul; Nabeel Khan Niazi (Journal of Soils and Sediments, 2016)

Uptake and distribution of minerals and heavy metals in commonly grown leafy vegetable species irrigated with sewage water - Sumera Anwar; Muhammad Farrakh Nawaz; Sadaf Gul; Muhammad Rizwan; Shafaqat Ali; Arshaad Kareem (Environmental Monitoring and Assessment, 2016)

Simultaneously removal of inorganic arsenic species from stored rainwater in arsenic endemic area by leaves of Tecomella undulata: a multivariate study - Kapil Dev Brahman; Tasneem Gul Kazi; Hassan Imran Afridi; Jameel Ahmed Baig; Muhammad Ishaque Abro; Sadaf Sadia Arain; Jamshed Ali; Sumaira Khan (Environmental Science and Pollution Research, 2016)

Inhibition of p90 ribosomal S6 kinase attenuates cell migration and proliferation of the human lung adenocarcinoma through phospho-GSK-3β and osteopontin - Nabeel Abdulrahman; Maiy Jaballah; Noufira Poomakkoth; Sadaf Riaz; Somaia Abdelaziz; Aya Issa; Fatima Mraiche (Molecular and Cellular Biochemistry, 2016)

Toxic Risk Assessment of Arsenic in Males Through Drinking Water in Tharparkar Region of Sindh, Pakistan - Kapil Dev Brahman; Tasneem Gul Kazi; Hassan Imran Afridi; Sadaf Sadia Arain; Atif Gul Kazi; Farah Naz Talpur; Jameel Ahmed Baig; Abdul Haleem Panhwar; Mariam Shezadi Arain; Jamshed Ali; Mohammad Balal Arain; Naeemullah (Biological Trace Element Research, 2016)

Correlation of cadmium and aluminum in blood samples of kidney disorder patients with drinking water and tobacco smoking: related health risk - Abdul Haleem Panhwar; Tasneem Gul Kazi; Hassan Imran Afridi; Salma Aslam Arain; Mariam Shahzadi Arain; Kapil Dev Brahaman; Naeemullah; Sadaf Sadia Arain (Environmental Geochemistry and Health, 2016)

Evaluation of calcium and lead interaction, in addition to their impact on thyroid functions in hyper and hypothyroid patients - Nusrat Shahab Memon; Tasneem Gul Kazi; Hassan Imran Afridi; Jameel Ahmed Baig; Sadaf Sadia Arain; Oan Muhammad Sahito; Shahnawaz Baloch; Muhammad Waris (Environmental Science and Pollution Research, 2016)

Evaluation of the fate of arsenic-contaminated groundwater at different aquifers of Thar coalfield Pakistan - Jamshed Ali; Tasneem G. Kazi; Jameel A. Baig; Hassan I. Afridi; Mariam S. Arain; Naeem Ullah; Kapil D. Brahman; Sadaf S. Arain; Abdul H. Panhwar (Environmental Science and Pollution Research, 2015)

Correlation of Arsenic Levels in Smokeless Tobacco Products and Biological Samples of Oral Cancer Patients and Control Consumers - Sadaf S. Arain; Tasneem G. Kazi; Hassan I. Afridi; Farah N. Talpur; Atif G. Kazi; Kapil D. Brahman; Naeemullah; Abdul H. Panhwar; Muhammad A. Kamboh (Biological Trace Element Research, 2015)

Tamoxifen-Induced Cell Death of Malignant Glioma Cells Is Brought About by Oxidative-Stress-Mediated Alterations in the Expression of BCL2 Family Members and Is Enhanced on miR-21 Inhibition - Mugdha Harmalkar; Shailendra Upraity; Sadaf Kazi; Neelam Vishwanath Shirsat (Journal of Molecular Neuroscience, 2015)

Erratum to: Preconcentration and determination of lead and cadmium levels in blood samples of adolescent workers consuming smokeless tobacco products in Pakistan - Sadaf Sadia Arain; Tasneem Gul Kazi; Hassan Imran Afridi; Kapil Dev Brahman; Naeemullah; Sumaira Khan; Abdul Haleem Panhwar; Muhammad Afzal Kamboh; Jamil R. Memon (Environmental Monitoring and Assessment, 2015)

Estimation of lead in biological samples of oral cancer patients chewing smokeless tobacco products by ionic liquid-based microextraction in a single syringe system - Sadaf S. Arain; Tasneem G. Kazi; Asma J. Arain; Hassan I. Afridi; Muhammad B. Arain; Kapil D. Brahman; Naeemullah; Abdul H. Panhwar; Mariam S. Arain (Environmental Science and Pollution Research, 2015)

Estimation of calcium, magnesium, cadmium, and lead in biological samples from paralyzed quality control and production steel mill workers - Hassan Imran Afridi; Farah Naz Talpur; Tasneem Gul Kazi; Naveed Kazi; Sadaf Sadia Arain; Faheem Shah (Environmental Monitoring and Assessment, 2015)

Environmental risk of heavy metal pollution and contamination sources using multivariate analysis in the soils of Varanasi environs, India - Shubhra Singh; N. Janardhana Raju; Sadaf Nazneen (Environmental Monitoring and Assessment, 2015)

Preconcentration and determination of lead and cadmium levels in blood samples of adolescent workers consuming smokeless tobacco products in Pakistan - Sadaf Sadia Arain; Tasneem Gul Kazi; Hassan Imran Afridi; Kapil Dev Brahman; Naeemullah; Sumaira Khan; Abdul Haleem Panhwar; Muhammad Afzal Kamboh; Jamil R. Memon (Environmental Monitoring and Assessment, 2015)

Differentiating neurons derived from human umbilical cord blood stem cells work as a test system for developmental neurotoxicity - Mahendra P. Kashyap; Vivek Kumar; Abhishek K. Singh; Vinay K. Tripathi; Sadaf Jahan; Ankita Pandey; Ritesh K. Srivastava; Vinay K. Khanna; Aditya B. Pant (Molecular Neurobiology, 2015)

Evaluated the Levels of Lead and Cadmium in Scalp Hair of Adolescent Boys Consuming Different Smokeless Tobacco Products with Related to Controls - Sadaf S. Arain; Tasneem G. Kazi; Asma J. Arain; Hassan I. Afridi; Kapil D. Brahman; Naeemullah; Jamshed Ali; G. Zuhra Memon (Biological Trace Element Research, 2015)

Assessment of selenium and mercury in biological samples of normal and night blindness children of age groups (3–7) and (8–12) years - Hassan Imran Afridi; Tasneem Gul Kazi; Farah Naz Talpur; Atif Kazi; Sadaf Sadia Arain; Salma Aslam Arain; Kapil Dev Brahman; Abdul Haleem Panhwar; Naeemullah Khan; Mariam Shazadi Arain; Jamshed Ali (Environmental Monitoring and Assessment, 2015)

Comparative evaluation of essential and toxic elements in the blood of kidney failure patients and healthy referents - Abdul Haleem Panhwar; Tasneem Gul Kazi; Hassan Imran Afridi; Salma Aslam Arain; Mariam S. Arain; Kapil Dev Brahman; Naeem Ullah; Jamshed Ali; Sadaf Sadia Arain (Environmental Monitoring and Assessment, 2015)

Hypoglycemic herbs and their polyherbal formulations: a comprehensive review - Deepti Katiyar; Vijender Singh; Sadaf J. Gilani; Richa Goel; Parul Grover; Amita Vats (Medicinal Chemistry Research, 2015)

Co-exposure of arsenic and cadmium through drinking water and tobacco smoking: Risk assessment on kidney dysfunction - Muhammad B. Arain; Tasneem G. Kazi; Jameel Ahmed Baig; Hassan I. Afridi; Sarajuddin; Kapil D. Brehman; Haleem Panhwar; Sadaf S. Arain (Environmental Science and Pollution Research, 2015)

Preferential Promotion of Lycopersicon esculentum (Tomato) Growth by Plant Growth Promoting Bacteria Associated with Tomato - Papa Rao Vaikuntapu; Swarnalee Dutta; Ram Babu Samudrala; Vukanti R. V. N. Rao; Sadaf Kalam; Appa Rao Podile (Indian Journal of Microbiology, 2014)

Evaluation of fresh and stored rainwater quality in fluoride and arsenic endemic area of Thar Desert, Pakistan - Kapil Dev Brahman; Tasneem Gul Kazi; Hassan Imran Afridi; Tahir Rafique; Jameel Ahmed Baig; Sadaf Sadia Arain; Naeem Ullah; Abdul Haleem Panhwar; Salma Arain (Environmental Monitoring and Assessment, 2014)

Harmful Effect of Detergents on Lipase - Sadaf Fatima; Rehan Ajmal; Gamal Badr; Rizwan H. Khan (Cell Biochemistry and Biophysics, 2014)

Genetic strategies to understand physiological pathways regulating body weight - Sadaf Farooqi (Mammalian Genome, 2014)

Determination of nickel in blood and serum samples of oropharyngeal cancer patients consumed smokeless tobacco products by cloud point extraction coupled with flame atomic absorption spectrometry - Sadaf Sadia Arain; Tasneem Gul Kazi; Jamshed Bashir Arain; Hassan Imran Afridi; Atif Gul Kazi; Syeda Nasreen; Kapil Dev Brahman (Environmental Science and Pollution Research, 2014)

Serotonergic neurons of the Drosophila air-puff-stimulated flight circuit - Sufia Sadaf; Gaiti Hasan (Journal of Biosciences, 2014)

Estimation of Copper and Iron Burden in Biological Samples of Various Stages of Hepatitis C and Liver Cirrhosis Patients - Salma Aslam Arain; Tasneem G Kazi; Hassan Imran Afridi; Farah Naz Talpur; Moina Akhtar Mughal; Faheem Shah; Sadaf Sadia Arain; Abdul Haleem Panhwar (Biological Trace Element Research, 2014)

Interaction Between Essential Elements Selenium and Zinc with Cadmium and Mercury in Samples from Hypertensive Patients - Hassan Imran Afridi; Tasneem Gul Kazi; Farah Naz Talpur; Atif Kazi; Sadaf Sadia Arain; Salma Aslam Arain; Kapil Dev Brahman; Abdul Haleem Panhwar; Naeemullah; Mariam Shezadi; Jamshed Ali (Biological Trace Element Research, 2014)

The adsorption process during inorganic phosphorus removal by cultured periphyton - Haiying Lu; Linzhang Yang; Sadaf Shabbir; Yonghong Wu (Environmental Science and Pollution Research, 2014)

Interaction Between Selenium and Mercury in Biological Samples of Pakistani Myocardial Infarction Patients at Different Stages as Related to Controls - Hassan Imran Afridi; Tasneem Gul Kazi; Farah Naz Talpur; Atif Kazi; Sadaf Sadia Arain; Salma Aslam Arain; Kapil Dev Brahman; Abdul Haleem Panhwar; Naeemullah (Biological Trace Element Research, 2014)

Potential Use of Low-Cost Lignocellulosic Waste for the Removal of Direct Violet 51 from Aqueous Solution: Equilibrium and Breakthrough Studies - Sana Sadaf; Haq Nawaz Bhatti; Sana Nausheen; Saima Noreen (Archives of Environmental Contamination and Toxicology, 2014)

Evaluation of peanut husk as a novel, low cost biosorbent for the removal of Indosol Orange RSN dye from aqueous solutions: batch and fixed bed studies - Sana Sadaf; Haq Nawaz Bhatti (Clean Technologies and Environmental Policy, 2014)

Use of a Fundamental Approach to Spray-Drying Formulation Design to Facilitate the Development of Multi-Component Dry Powder Aerosols for Respiratory Drug Delivery - Susan Hoe; James W. Ivey; Mohammed A. Boraey; Abouzar Shamsaddini-Shahrbabak; Emadeddin Javaheri; Sadaf Matinkhoo; Warren H. Finlay; Reinhard Vehring (Pharmaceutical Research, 2014)

A non-ionic surfactant reduces the induction time and enhances expression levels of bubaline somatotropin in Pichia pastoris - Saima Sadaf; Hammad Arshad; M. Waheed Akhtar (Molecular Biology Reports, 2014)

Exposure of lead to mothers and their new born infants, residents of industrial and domestic areas of Pakistan - Tasneem G. Kazi; Faheem Shah; Haffeezur Rehman Shaikh; Hassan Imran Afridi; Afzal Shah; Naeemullah; Sadaf Sadia Arain (Environmental Science and Pollution Research, 2014)

Threat of glacial lake outburst flood to Tehsil Gupis from Khukush Lake, District Ghizer, Gilgit Baltistan, Pakistan - Gohar Rehman; Sajjad Ahmad; Shuhab D. Khan; Fayaz Ali; Taqweemul H. Ali; Sadaf F. Khan (Natural Hazards, 2014)

Evaluation of Calcium and Magnesium in Scalp Hair Samples of Population Consuming Different Drinking Water: Risk of Kidney Stone - Abdul Haleem Panhwar; Tasneem Gul Kazi; Hassan Imran Afridi; Haffeezur Rehman Shaikh; Salma Aslam Arain; Sadaf Sadia Arain; Kapil Dev Brahman (Biological Trace Element Research, 2013)

Investigation of Alteration in the Levels of Iron and Copper in Scalp Hair Samples of Patients Having Different Types of Viral Hepatitis - Salma Aslam Arain; Hassan Imran Afridi; Tasneem G. Kazi; Farah Naz Talpur; Faheem Shah; Sadaf Sadia Arain; Abdul Haleem Panhwar; Kapil Dev Brahman (Biological Trace Element Research, 2013)

3-Methylcholanthrene Induces Neurotoxicity in Developing Neurons Derived from Human CD34+Thy1+ Stem Cells by Activation of Aryl Hydrocarbon Receptor - Abhishek K. Singh; Mahendra P. Kashyap; Vivek Kumar; Vinay K. Tripathi; Dharmendra K. Yadav; Firoz Khan; Sadaf Jahan; Vinay K. Khanna; Sanjay Yadav; Aditya B. Pant (NeuroMolecular Medicine, 2013)

SLC26A4 Mutations in Patients with Moderate to Severe Hearing Loss - Muhammad Riaz Khan; Rasheeda Bashir; Sadaf Naz (Biochemical Genetics, 2013)

Contribution of GJB2 Mutations to Hearing Loss in the Hazara Division of Pakistan - Ihtisham Bukhari; Ghulam Mujtaba; Sadaf Naz (Biochemical Genetics, 2013)

Synthesis and pharmacological evaluation of N-(6-chlorobenzo[d]thiazol-2-yl)hydrazine carboxamide derivatives of benzothiazole - Sadaf J. Gilani; Suroor A. Khan (Medicinal Chemistry Research, 2013)

Association of interleukin-18 gene variants with susceptibility to visceral leishmaniasis in Iranian population - Ali Moravej; Manoochehr Rasouli; Sadaf Asaei; Mehdi Kalani; Yaser Mansoori (Molecular Biology Reports, 2013)

Analysis of cadmium, nickel, and lead in commercial moist and dry snuff used in Pakistan - Tasneem Gul Kazi; Sadaf Sadia Arain; Hassan Imran Afridi; Naeemullah; Kapil Dev Brahman; Nida Fatima Kolachi; Moina Akhtar Mughal (Environmental Monitoring and Assessment, 2013)

The c.42_52del11 Mutation in TPRN and Progressive Hearing Loss in a Family from Pakistan - Rasheeda Bashir; Ayesha Imtiaz; Amara Fatima; Afzaal Alam; Sadaf Naz (Biochemical Genetics, 2013)

The improvement of anti-proliferation activity against breast cancer cell line of thioguanine by gold nanoparticles - Sadaf Aghevlian; Reza Yousefi; Reza Faghihi; Abdolkarim Abbaspour; Ali Niazi; Mansooreh Jaberipour; Ahmad Hosseini (Medicinal Chemistry Research, 2013)

Immunoassays Based on Surface-Enhanced Fluorescence using Gap-Plasmon-Tunable Ag Bilayer Nanoparticle Films - Ruohu Zhang; Zhuyuan Wang; Chunyuan Song; Jing Yang; Asma Sadaf; Yiping Cui (Journal of Fluorescence, 2013)

Genotoxicity Assessment of Amaranth and Allura Red Using Saccharomyces Cerevisiae - Hafiza Sumara Jabeen; Sajjad ur Rahman; Shahid Mahmood; Sadaf Anwer (Bulletin of Environmental Contamination and Toxicology, 2013)

Effects of Mineral Supplementation on Liver Cirrhotic/Cancer Male Patients - Tasneem Gul Kazi; Nida Fatima Kolachi; Hassan Imran Afridi; Naveed Gul Kazi; Sirajuddin; Naeemullah; Sadaf Sadia Arain (Biological Trace Element Research, 2012)

Stratigraphic and palaeoenvironmental framework of the Early Permian sequence in the Salt Range, Pakistan - SHAHID GHAZI; NIGEL P MOUNTNEY; AFTAB AHMAD BUTT; SADAF SHARIF (Journal of Earth System Science, 2012)

VEGF gene mRNA expression in patients with coronary artery disease - Mahsa M. Amoli; Parvin Amiri; Amin Alborzi; Bagher Larijani; Sadaf Saba; Javad Tavakkoly-Bazzaz (Molecular Biology Reports, 2012)

Petrographic and geochemical characteristics of Mesoproterozoic Kumbalgarh clastic rocks, NW Indian shield: implications for provenance, tectonic setting, and crustal evolution - Sadaf Fatima; M. Shamim Khan (International Geology Review, 2012)

IL-1β (−511T/C) gene polymorphism not IL-1β (+3953T/C) and LT-α (+252A/G) gene variants confers susceptibility to visceral leishmaniasis - Ali Moravej; Manoochehr Rasouli; Mehdi Kalani; Sadaf Asaei; Simin Kiany; Sohrab Najafipour; Amin Koohpayeh; Abbas Abdollahi (Molecular Biology Reports, 2012)

The effect of temperature and substrate on the development of the cortisol stress response in the lake sturgeon, Acipenser fulvescens, Rafinesque (1817) - Sadaf N. Zubair; Stephan J. Peake; James F. Hare; W. Gary Anderson (Environmental Biology of Fishes, 2012)

pH-Induced Molten Globule State of Rhizopus niveus Lipase is More Resistant Against Thermal and Chemical Denaturation Than Its Native State - Gulam Rabbani; Ejaz Ahmad; Nida Zaidi; Sadaf Fatima; Rizwan Hasan Khan (Cell Biochemistry and Biophysics, 2012)

Immunodetection of cyclooxygenase-2 (COX-2) is restricted to tissue macrophages in normal rat liver and to recruited mononuclear phagocytes in liver injury and cholangiocarcinoma - Marta Wójcik; Pierluigi Ramadori; Martina Blaschke; Sadaf Sultan; Sajjad Khan; Ihtzaz A. Malik; Naila Naz; Gesa Martius; Giuliano Ramadori; Frank C. Schultze (Histochemistry and Cell Biology, 2012)

Phylogenetic and structural analysis of HCV nonstructural protein 4A from Pakistani patients - Najam us Sahar Sadaf Zaidi; Naghmana Kanwal; Awaisa Ghazal; Kaneez Fatima; Farakh Javed; Ishtiaq Qadri (Virus Genes, 2012)

A molecular evaluation of dengue virus pathogenesis and its latest vaccine strategies - Muhammad Faheem; Ummar Raheel; Muhammad Nasir Riaz; Naghmana Kanwal; Farakh Javed; Najam us Sahar Sadaf Zaidi; Ishtiaq Qadri (Molecular Biology Reports, 2011)

Myeloperoxidase and elastase are only expressed by neutrophils in normal and in inflammed liver - Ahmad Amanzada; Ihtzaz Ahmed Malik; Martin Nischwitz; Sadaf Sultan; Naila Naz; Giuliano Ramadori (Histochemistry and Cell Biology, 2011)

Arabidopsis thaliana GH3.9 influences primary root growth - Sadaf Khan; Julie M. Stone (Planta, 2007)

Novel mutations of MYO15A associated with profound deafness in consanguineous families and moderately severe hearing loss in a patient with Smith-Magenis syndrome - Nikki Liburd; Manju Ghosh; Saima Riazuddin; Sadaf Naz; Shaheen Khan; Zubair Ahmed; Sheikh Riazuddin; Yong Liang; Puthezhath Menon; Tenesha Smith; Ann Smith; Ken-Shiung Chen; et al. (Human Genetics, 2001)